Epoxy resin, curable composition, metal-clad laminate and printed circuit board

By using a combination of fluoropolymer and epoxy resin in the printed substrate, the problem of insufficient electrical characteristics and heat resistance in the high-frequency band region of the printed substrate in the prior art is solved, and better electrical performance and high-frequency adaptability are achieved.

CN119735734APending Publication Date: 2025-04-01DAIKIN INDUSTRIES LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411912781.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-10-30
Filing Date
2020-08-06
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The electrical characteristics, heat resistance and solder resistance of existing printed substrates in the high-frequency band region are insufficient, making it difficult to meet the demand for the high-frequency band region of modern electrical and electronic equipment.

Method used

A fluoropolymer for metal-covered laminate is used, which comprises polymerized units based on fluorine-containing vinyl monomer and vinyl ester monomer, has excellent compatibility with an epoxy resin, and improves the low dielectric constant and low dielectric loss tangent of the resin layer through the active ester function.

Benefits of technology

The low dielectric constant and low dielectric loss angle tangent of the metal-covered laminate resin layer are achieved, which enhances its adaptability to the frequency of the high frequency band region, and improves insulation, adhesion, heat resistance and flame retardancy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206144950000031
    Figure BDA0005206144950000031
  • Figure BDA0005206144950000041
    Figure BDA0005206144950000041
  • Figure BDA0005206144950000061
    Figure BDA0005206144950000061
Patent Text Reader

Abstract

The present invention provides an epoxy resin, a curable composition, a metal-clad laminate and a printed circuit board. An epoxy resin comprising a polymerized unit based on tetrafluoroethylene and / or a polymerized unit based on hexafluoropropylene, and a polymerized unit based on allyl glycidyl ether, wherein the total content of the polymerized unit based on tetrafluoroethylene, the polymerized unit based on hexafluoropropylene and the polymerized unit based on allyl glycidyl ether is 98 mol% to 100 mol% relative to the total polymerized units, and the polymerized unit based on allyl glycidyl ether is 40 mol% or more relative to the total polymerized units.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The Chinese national application number of the application to which it is directed is 202080055922.6, the international application number is PCT / JP2020 / 030199, the application date is August 6, 2020, the date of entry into China is February 7, 2022, and the name of the invention is "Fluoropolymers for metal-clad laminates, compositions for metal-clad laminates, curable compositions, metal-clad laminates and printed substrates". Technical Field

[0002] The present disclosure relates to a fluorine-containing polymer for a metal-clad laminate, a composition for a metal-clad laminate, a curable composition, a metal-clad laminate, and a printed circuit board. Background Art

[0003] In recent years, electrical equipment, electronic equipment, and communication equipment have achieved very remarkable development. Currently, there is a tendency to use frequencies in higher frequency bands in these devices. In addition, various printed circuit boards are generally used in these devices. Therefore, printed circuit boards are also required to have excellent electrical properties corresponding to frequencies in the high frequency band, excellent heat resistance that can withstand soldering operations, etc. In the case where the printed circuit board is a laminate consisting of two layers, a base material and a copper foil layer, polyimide is used in the base material, and epoxy resin, acrylic resin, etc. are used in the adhesive layer, but the insulation, adhesion, and heat resistance are insufficient, and research has been conducted on this.

[0004] For example, Patent Document 1 describes, with the purpose of providing a metal-clad laminate having a metal foil firmly bonded to a substrate and exhibiting excellent electrical properties: a metal-clad laminate comprising a metal foil and a first resin layer provided on the metal foil, characterized in that the first resin layer is composed of an epoxy resin and a fluorine-containing polymer having a curable functional group; and a flexible printed substrate comprising a pattern circuit formed by etching the metal foil of the metal-clad laminate.

[0005] Patent Document 2 describes: an active ester compound having a specific structure; and a thermosetting resin composition characterized in that it contains: an active ester compound component containing at least one active ester compound, and an epoxy resin component containing at least one epoxy resin.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2012-106491

[0009] Patent Document 2: Japanese Patent Application Publication No. 2006-307091 Summary of the invention

[0010] Problems to be solved by the invention

[0011] The present invention provides a fluorine-containing polymer for a metal-clad laminate having excellent compatibility with an epoxy resin.

[0012] Means for solving problems

[0013] The present disclosure provides a fluorine-containing polymer for metal-clad laminates (hereinafter also recorded as "the first fluorine-containing polymer of the present disclosure"), characterized in that it contains polymerization units based on fluorine-containing vinyl monomers and polymerization units based on vinyl ester monomers (excluding the above-mentioned fluorine-containing vinyl monomers), and the total of polymerization units based on monomers containing hydroxyl groups and polymerization units based on monomers containing carboxyl groups is less than 1 mol% relative to all polymerization units.

[0014] The present disclosure also provides a composition for a metal-clad laminate (hereinafter also referred to as "a first composition for a metal-clad laminate of the present disclosure"), characterized in that it contains the first fluorinated polymer of the present disclosure and a solvent.

[0015] The present disclosure also provides a curable composition (hereinafter also described as "the first curable composition of the present disclosure"), characterized in that it contains a fluorine-containing polymer and an epoxy resin, the fluorine-containing polymer contains polymerization units based on a fluorine-containing vinyl monomer, and polymerization units based on a vinyl ester (wherein the polymerization units based on the above-mentioned fluorine-containing vinyl monomer are not included), and the total of polymerization units based on monomers containing hydroxyl groups and polymerization units based on monomers containing carboxyl groups is less than 1 mol% relative to all polymerization units.

[0016] The first curable composition of the present disclosure preferably further contains a solvent.

[0017] The first curable composition of the present disclosure preferably contains 1 to 1000 parts by mass of the epoxy resin based on 100 parts by mass of the fluorinated polymer.

[0018] The first curable composition of the present disclosure preferably further contains a curing accelerator.

[0019] The polymerized units based on the vinyl ester monomer preferably account for 10 mol% or more of all the polymerized units of the fluorinated polymer.

[0020] The above vinyl ester monomer is preferably of the following formula:

[0021] CH2=CH-OC(=O)-R A

[0022] (Where R AA monomer represented by an alkyl group having 1 to 4 carbon atoms or a phenyl group which may have a substituent.

[0023] The vinyl ester monomer is preferably at least one selected from the group consisting of vinyl benzoate, vinyl p-tert-butylbenzoate, vinyl acetate, and vinyl pivalate.

[0024] The polymerized units based on the fluorine-containing vinyl monomer preferably account for 10 mol% or more of all the polymerized units of the fluorine-containing polymer.

[0025] The fluorine-containing vinyl monomer is preferably at least one selected from the group consisting of tetrafluoroethylene, chlorotrifluoroethylene, vinyl fluoride, hexafluoropropylene and perfluoro(alkyl vinyl ether).

[0026] The first fluorinated polymer disclosed in the present invention preferably further comprises a polymerized unit based on a monomer other than the above-mentioned fluorinated vinyl monomer and the above-mentioned vinyl ester monomer.

[0027] In the first fluorinated polymer disclosed herein, the monomer other than the above-mentioned fluorinated vinyl monomer and the above-mentioned vinyl ester monomer preferably comprises the following general formula (2):

[0028] [Chemistry 1]

[0029]

[0030] (Where X B is a monomer represented by H or CH3).

[0031] The first fluorine-containing polymer disclosed in the present invention preferably has a number average molecular weight of 1,000 to 30,000.

[0032] The present disclosure also provides a metal-clad laminate (hereinafter also referred to as "the first metal-clad laminate of the present disclosure"), which is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, characterized in that the resin layer is formed from the curable composition.

[0033] The present disclosure further provides a printed circuit board (hereinafter also described as "the first printed circuit board of the present disclosure") characterized by comprising a pattern circuit formed by etching the metal foil of the metal-clad laminate.

[0034] The present disclosure also provides a fluorine-containing polymer (hereinafter also described as "the second fluorine-containing polymer of the present disclosure"), characterized in that it contains polymerization units based on tetrafluoroethylene and polymerization units based on vinyl ester monomers, the chain segments of tetrafluoroethylene unit-vinyl ester unit-tetrafluoroethylene unit are 45 mol% or more, and the total of polymerization units based on monomers containing hydroxyl groups and polymerization units based on monomers containing carboxyl groups is 1 mol% or less relative to all polymerization units.

[0035] The second fluorinated polymer disclosed in the present invention preferably has a number average molecular weight of 15,000 or less.

[0036] In the second fluorinated polymer of the present disclosure, the content of the polymerized units based on the vinyl ester monomer is preferably 10 mol% or more based on the total polymerized units of the fluorinated polymer.

[0037] In the second fluorinated polymer disclosed herein, the vinyl ester monomer is preferably of the following formula:

[0038] CH2=CH-OC(=O)-R A

[0039] (Where R A A monomer represented by an alkyl group having 1 to 4 carbon atoms or a phenyl group which may have a substituent.

[0040] In the second fluorine-containing polymer of the present disclosure, the vinyl ester monomer is preferably at least one selected from the group consisting of vinyl benzoate, vinyl p-tert-butylbenzoate, vinyl acetate and vinyl pivalate.

[0041] In the second fluorinated polymer disclosed herein, the content of the polymerized units derived from tetrafluoroethylene is preferably 10 mol% or more based on the total polymerized units of the fluorinated polymer.

[0042] The second fluorinated polymer disclosed in the present disclosure preferably further contains polymerized units based on a monomer other than the above-mentioned tetrafluoroethylene and the above-mentioned vinyl ester monomer.

[0043] In the second fluorinated polymer disclosed herein, the monomer other than the above-mentioned tetrafluoroethylene and the above-mentioned vinyl ester monomer preferably comprises the following general formula (2):

[0044] [Chemistry 2]

[0045]

[0046] (Where X B is a monomer represented by H or CH3).

[0047] The present disclosure further provides a composition for a metal-clad laminate (hereinafter also described as "a second composition for a metal-clad laminate of the present disclosure") characterized by comprising the second fluorinated polymer of the present disclosure and a solvent.

[0048] The present disclosure also provides a curable composition (hereinafter also referred to as "the second curable composition of the present disclosure") characterized by comprising the second fluorinated polymer of the present disclosure and an epoxy resin.

[0049] The second curable composition of the present disclosure preferably further contains a solvent.

[0050] The second curable composition of the present disclosure preferably contains 1 to 1000 parts by mass of the epoxy resin based on 100 parts by mass of the fluorinated polymer.

[0051] The second curable composition of the present disclosure preferably further contains a curing accelerator.

[0052] The present disclosure further provides a metal-clad laminate (hereinafter also referred to as "the second metal-clad laminate of the present disclosure"), which is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, characterized in that the resin layer is formed from the curable composition.

[0053] The present disclosure also provides a printed circuit board (hereinafter also referred to as "a second printed circuit board of the present disclosure") characterized in that it includes a pattern circuit formed by etching the metal foil of the metal-clad laminate.

[0054] The present disclosure also provides a fluorine-containing polymer (hereinafter also described as "the third fluorine-containing polymer of the present disclosure"), characterized in that it contains polymerization units based on a fluorine-containing vinyl monomer and polymerization units based on a vinyl ester monomer, the total content of the polymerization units based on the fluorine-containing vinyl monomer and the polymerization units based on the vinyl ester monomer is 70 to 100 mol% relative to all the polymerization units, the fluorine-containing vinyl monomer contains at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene and chlorotrifluoroethylene, and when the fluorine-containing vinyl monomer contains tetrafluoroethylene, the integral value of CF2H at the -CF2H terminal in 19F-NMR relative to the integral value of the entire CF2 is 2% or less, when the fluorine-containing vinyl monomer contains hexafluoropropylene, the integral value of CFH at the -CF2CFHCF3 terminal in 19F-NMR relative to the integral value of the entire CF is 2% or less, and when the fluorine-containing vinyl monomer contains chlorotrifluoroethylene, the total integral value of CF2H at the -CF2H terminal and the integral value of CFClH at the -CFClH terminal in 19F-NMR relative to the total integral value of CF2 and the integral value of CFCl is 2% or less.

[0055] The third fluorine-containing polymer disclosed in the present invention preferably has a number average molecular weight of 1,000 to 600,000.

[0056] In the third fluorinated polymer of the present disclosure, the polymerized units based on the vinyl ester monomer preferably account for 10 mol% or more of all the polymerized units of the fluorinated polymer.

[0057] In the third fluorine-containing polymer of the present disclosure, the vinyl ester monomer is preferably of the following formula:

[0058] CH2=CH-OC(=O)-R A

[0059] (Where R A A monomer represented by an alkyl group having 1 to 4 carbon atoms or a phenyl group which may have a substituent.

[0060] In the third fluorine-containing polymer of the present disclosure, the vinyl ester monomer is preferably at least one selected from the group consisting of vinyl benzoate, vinyl p-tert-butylbenzoate, vinyl acetate and vinyl pivalate.

[0061] In the third fluorinated polymer of the present disclosure, the content of the polymerized units based on the fluorinated vinyl monomer is preferably 10 mol% or more based on the total polymerized units of the fluorinated polymer.

[0062] The third fluorine-containing polymer of the present disclosure preferably further contains polymerized units based on a monomer other than the above-mentioned fluorine-containing vinyl monomer and the above-mentioned vinyl ester monomer.

[0063] In the third fluorine-containing polymer of the present disclosure, the monomer other than the above-mentioned fluorine-containing vinyl monomer and the above-mentioned vinyl ester monomer preferably comprises the following general formula (2):

[0064] [Chemistry 3]

[0065]

[0066] (Where X B is a monomer represented by H or CH3).

[0067] The present disclosure also provides a composition for a metal-clad laminate (hereinafter also described as "a third composition for a metal-clad laminate of the present disclosure"), characterized in that it contains the third fluorinated polymer of the present disclosure and a solvent.

[0068] The present disclosure also provides a curable composition (hereinafter also referred to as "the third curable composition of the present disclosure") characterized by comprising the third fluorinated polymer of the present disclosure and an epoxy resin.

[0069] The third curable composition of the present disclosure preferably further contains a solvent.

[0070] The third curable composition of the present disclosure preferably contains 1 to 1000 parts by mass of the epoxy resin based on 100 parts by mass of the fluorinated polymer.

[0071] The third curable composition of the present disclosure preferably further contains a curing accelerator.

[0072] The present disclosure also provides a metal-clad laminate (hereinafter also referred to as "the third metal-clad laminate of the present disclosure"), which is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, characterized in that the resin layer is formed from the curable composition.

[0073] The present disclosure also provides a printed circuit board (hereinafter also described as "a third printed circuit board of the present disclosure") characterized in that it includes a pattern circuit formed by etching the metal foil of the above-mentioned metal-clad laminate.

[0074] The present disclosure also provides an epoxy resin (hereinafter also described as "the epoxy resin of the present disclosure"), characterized in that it contains polymerization units based on tetrafluoroethylene and / or polymerization units based on hexafluoropropylene, and polymerization units based on allyl glycidyl ether, and the total content of the above-mentioned polymerization units based on tetrafluoroethylene, the above-mentioned polymerization units based on hexafluoropropylene and the above-mentioned polymerization units based on allyl glycidyl ether is 98 to 100 mol% relative to all polymerization units.

[0075] The epoxy resin disclosed herein is preferably liquid at 25° C. and also preferably has a number average molecular weight of 500 to 10,000.

[0076] When the epoxy resin disclosed in the present invention contains a polymerization unit based on tetrafluoroethylene, the integral value of CF2H at the -CF2H terminal in 19F-NMR is preferably 4% or less relative to the integral value of CF2 as a whole; when it contains a polymerization unit based on hexafluoropropylene, the integral value of CFH at the -CF2CFHCF3 terminal in 19F-NMR is preferably 4% or less relative to the integral value of CF as a whole.

[0077] In the epoxy resin of the present disclosure, the polymerized units based on allyl glycidyl ether preferably account for 10 mol% or more of all the polymerized units of the epoxy resin.

[0078] In the epoxy resin of the present disclosure, the total content of the polymerized units based on tetrafluoroethylene and the polymerized units based on hexafluoropropylene is preferably 10 mol% or more based on the total polymerized units of the epoxy resin.

[0079] The present disclosure also provides a curable composition (hereinafter also referred to as “the fourth curable composition of the present disclosure”) characterized by comprising the epoxy resin of the present disclosure and a fluorine-containing polymer.

[0080] The fourth curable composition of the present disclosure preferably further contains a solvent.

[0081] The fourth curable composition of the present disclosure preferably contains 1 to 1000 parts by mass of the epoxy resin based on 100 parts by mass of the fluorinated polymer.

[0082] The fourth curable composition of the present disclosure preferably further contains a curing accelerator.

[0083] The present disclosure also provides a metal-clad laminate (hereinafter also referred to as "the fourth metal-clad laminate of the present disclosure"), which is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, characterized in that the resin layer is formed from the curable composition.

[0084] The present disclosure also provides a printed circuit board (hereinafter also described as "a fourth printed circuit board of the present disclosure") characterized in that it includes a pattern circuit formed by etching the metal foil of the metal-clad laminate.

[0085] Effects of the Invention

[0086] The fluorinated polymer for metal-clad laminates disclosed herein, the second fluorinated polymer disclosed herein, and the third fluorinated polymer disclosed herein have excellent compatibility with epoxy resins. In addition, the epoxy resin disclosed herein has excellent compatibility with fluorinated polymers. DETAILED DESCRIPTION

[0087] In the metal-clad laminate of Patent Document 1, the first resin layer is formed of an epoxy resin and a fluorine-containing polymer having a curable functional group, thereby providing a metal-clad laminate in which the metal foil is firmly bonded to the substrate and exhibits excellent electrical properties. However, there is still room for improvement in terms of compatibility with the epoxy resin.

[0088] Patent document 2 discloses, as an active ester compound, a compound having a group (active ester group) formed by esterification of a phenolic hydroxyl group with an aromatic acid or a fatty acid, but does not disclose other hydroxyl-containing resins. In order to further improve the performance of low dielectric constant and low dielectric loss tangent, there is still room for improvement.

[0089] The fluorine-containing polymer for metal-clad laminates disclosed in the present invention (the first fluorine-containing polymer disclosed in the present invention) comprises polymerization units based on fluorine-containing vinyl monomers and polymerization units based on vinyl ester monomers (excluding the above-mentioned fluorine-containing vinyl monomers), and the total of polymerization units based on monomers containing -OH groups and polymerization units based on monomers containing -COOH groups is less than 1 mol% relative to all polymerization units, thereby making it excellent in compatibility with epoxy resins. In addition, the above-mentioned fluorine-containing polymer can function as an active ester, so that the resin layer of the metal-clad laminate can have a low dielectric constant and a low dielectric loss tangent. In addition, the resin layer of the metal-clad laminate can also be firmly bonded to the metal foil. According to the in-depth research of the inventors, it was found that the above-mentioned fluorine-containing polymer has the above-mentioned characteristics and is particularly suitable as a polymer for metal-clad laminates (polymer for the resin layer of metal-clad laminates).

[0090] The present disclosure provides use of the above-mentioned fluorine-containing polymer in a metal-clad laminate (resin layer of the metal-clad laminate).

[0091] The first fluorinated polymer of the present disclosure comprises polymerized units based on a fluorinated vinyl monomer (hereinafter referred to as “fluorinated vinyl monomer units”).

[0092] As the above-mentioned fluorine-containing vinyl monomer, it is preferably at least one selected from the group consisting of tetrafluoroethylene [TFE], trifluorochloroethylene [CTFE], fluoroethylene, hexafluoropropylene [HFP] and perfluoro (alkyl vinyl ether), and more preferably at least one selected from the group consisting of TFE, CTFE, fluoroethylene, HFP and perfluoro (alkyl vinyl ether). From the aspects of having low dielectric constant and low dielectric loss tangent and excellent dispersibility, moisture resistance, heat resistance, flame retardancy, adhesion and chemical resistance, and from the aspects of having low dielectric constant and low dielectric loss tangent and excellent weather resistance and moisture resistance, it is more preferably at least one selected from the group consisting of TFE, CTFE and HFP, from the aspect of not containing chlorine, it is more preferably at least one selected from the group consisting of TFE and HFP, and from the aspect of excellent copolymerizability, TFE is particularly preferred.

[0093] Examples of the perfluoro(alkyl vinyl ether) include perfluoro(methyl vinyl ether) [PMVE], perfluoro(ethyl vinyl ether) [PEVE], perfluoro(propyl vinyl ether) [PPVE], and perfluoro(butyl vinyl ether), but are not limited thereto.

[0094] From the perspective of excellent low dielectric constant and low dielectric loss tangent, the above-mentioned fluorinated vinyl monomer unit is preferably 10 mol% or more, more preferably 20 mol% or more, further preferably 30 mol% or more, even more preferably 40 mol% or more, particularly preferably 50 mol% or more, and is preferably 80 mol% or less, more preferably 70 mol% or less, and further preferably 60 mol% or less, relative to all the polymerized units constituting the above-mentioned fluorinated polymer.

[0095] The first fluorine-containing polymer disclosed herein comprises polymerized units based on vinyl ester monomers (but not including fluorine-containing vinyl monomers) (hereinafter referred to as "vinyl ester monomer units"). By comprising the vinyl ester monomer units, active esters can be generated and react with epoxy resins.

[0096] Examples of the vinyl ester monomer include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caproate, vinyl versatate, vinyl laurate, vinyl stearate, vinyl cyclohexylcarboxylate, vinyl benzoate, and vinyl p-tert-butylbenzoate.

[0097] As the vinyl ester monomer, the following formula (A) is preferred because of high reactivity of active esters:

[0098] CH2=CH-OC(=O)-R A (A)

[0099] (Where R A is an alkyl group having 1 to 4 carbon atoms or a phenyl group which may have a substituent)

[0100] The monomer represented.

[0101] The above R A The alkyl group is an alkyl group having 1 to 4 carbon atoms, and the alkyl group has 1 to 2 carbon atoms, and more preferably 1 carbon atom.

[0102] As the above R A The substituent that the phenyl group may have includes an alkyl group having 1 to 4 carbon atoms, an alkoxy group, a dialkylamino group, and the like, and a tert-butyl group is preferred.

[0103] Due to the high reactivity of active esters, the above-mentioned vinyl ester monomer is preferably at least one selected from the group consisting of vinyl benzoate, vinyl p-tert-butylbenzoate, vinyl acetate and vinyl pivalate, and more preferably at least one selected from the group consisting of vinyl benzoate, vinyl p-tert-butylbenzoate and vinyl acetate.

[0104] The vinyl ester monomer unit is preferably 20 mol% or more relative to the total polymerized units of the fluorinated polymer for reasons of excellent compatibility and reactivity with the epoxy resin. The vinyl ester monomer unit is more preferably 30 mol% or more, and further preferably 40 mol% or more relative to the total polymerized units, and is preferably 80 mol% or less, more preferably 70 mol% or less, and further preferably 60 mol% or less for reasons of excellent heat resistance.

[0105] In the first fluorinated polymer disclosed in the present invention, the polymerized units based on the monomer represented by the above formula (A) are preferably 10 to 100 mol% relative to the total 100 mol% of the above vinyl ester monomer units, and the polymerized units based on the vinyl ester monomers other than the monomer represented by the above formula (A) are preferably 0 to 90 mol%. The polymerized units based on the monomer represented by the above formula (A) are more preferably 20 to 90 mol%, further preferably 30 to 80 mol%, further more preferably 35 to 75 mol%, and particularly preferably 40 to 70 mol% relative to the total 100 mol% of the above vinyl ester monomer units. The polymerized units based on the vinyl ester monomers other than the monomer represented by the above formula (A) are more preferably 10 to 80 mol%, further preferably 20 to 70 mol%, further more preferably 25 to 65 mol%, and particularly preferably 30 to 60 mol% relative to the total 100 mol% of the above vinyl ester monomer units.

[0106] From the perspective of being used in metal-clad laminates, excellent heat resistance is required. Therefore, as a vinyl ester monomer other than the monomer represented by the above formula (A), a vinyl ester monomer that can increase the glass transition temperature by crosslinking is preferred. For example, vinyl cinnamate, β-styryl vinyl acrylate, β-furyl vinyl acrylate, p-azidocinnamate vinyl ester, etc. can be mentioned.

[0107] The above-mentioned vinyl ester monomer may not contain a hydroxyl group and a carboxyl group.

[0108] The first fluorinated polymer of the present disclosure may further contain polymerized units (hereinafter referred to as “other monomer units”) based on monomers (hereinafter referred to as “other monomers”) other than the above-mentioned fluorinated vinyl monomer and the above-mentioned vinyl ester monomer.

[0109] Examples of the other monomers include alkyl vinyl ethers not containing a hydroxyl group, non-fluorinated olefins not containing a halogen atom and a hydroxyl group, amino group-containing monomers not containing an NH group, hydrolyzable silyl group-containing monomers not containing an OH group, epoxy group-containing monomers, oxetane group-containing monomers, heterocyclic ring-containing monomers, and (meth)acrylate monomers.

[0110] As the (meth)acrylate, aromatic esters and alicyclic esters of (meth)acrylic acid are preferred from the viewpoint of being able to increase the glass transition temperature of the polymer, and the following general formula (2) is particularly preferred:

[0111] [Chemistry 4]

[0112]

[0113] (Where X BA monomer (2) represented by H or CH3), phenyl (meth)acrylate. In addition, from the viewpoint of being able to function as an active ester, an aromatic ester of (meth)acrylic acid is preferred, and phenyl (meth)acrylate is preferred.

[0114] In the present disclosure, "(meth)acrylic acid" means methacrylic acid or acrylic acid.

[0115] Examples of the alkyl vinyl ether not containing a hydroxyl group include methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, n-butyl vinyl ether, octadecyl vinyl ether, 2-ethylhexyl vinyl ether, cyclohexyl vinyl ether, isopropyl vinyl ether, isobutyl vinyl ether, and the like. Among them, at least one selected from the group consisting of ethyl vinyl ether and cyclohexyl vinyl ether is preferred.

[0116] Examples of the non-fluorinated olefin not containing a halogen atom and a hydroxyl group include ethylene, propylene, n-butene, isobutylene and the like.

[0117] Examples of the amino group-containing monomer include CH2=CH-O-(CH2) x -Amino vinyl ethers represented by NH2 (x = 0 to 10); CH2 = CH-O-CO (CH2) x -Amines represented by NH2 (x=1 to 10); and aminomethylstyrene, vinylamine, acrylamide, vinylacetamide, vinylformamide, etc.

[0118] Examples of the above-mentioned monomers containing a hydrolyzable silyl group include CH2=CHCO2(CH2)3Si(OCH3)3, CH2=CHCO2(CH2)3Si(OC2H5)3, CH2=C(CH3)CO2(CH2)3Si(OCH3)3, CH2=C(CH3)CO2(CH2)3Si(OC2H5)3, CH2=CHCO2(CH2)3SiCH3(OC2H5)2, CH2=C(CH3)CO2(CH2)3SiC2H5(OC H3)2, CH2=C(CH3)CO2(CH2)3Si(CH3)2(OC2H5), CH2=C(CH3)CO2(CH2)3Si(CH3)2OH, CH2=CH(CH2)3Si(OCOCH3)3, C H2=C(CH3)CO2(CH2)3SiC2H5(OCOCH3)2, CH2=C(CH3)CO2(CH2)3SiCH3(N(CH3)COCH3)2, CH2=CHCO2(CH2)3SiCH3[O (Meth)acrylates such as N(CH3)C2H5]2, CH2=C(CH3)CO2(CH2)3SiC6H5[ON(CH3)C2H5]2; CH2=CHSi[ON=C(CH3)(C2H5)]3, CH2=CHSi(OCH3)3, CH2=CHSi(OC2H5)3, CH2=CHSiCH3(OCH3)2, CH2=CHSi(OCOCH3)3, CH2=CHSi(CH3)2(OC2H5), CH2=CHSi Vinyl silanes such as (CH3)2SiCH3(OCH3)2, CH2=CHSiC2H5(OCOCH3)2, CH2=CHSiCH3[ON(CH3)C2H5]2, vinyltrichlorosilane or their partial hydrolyzates; vinyl ethers such as trimethoxysilylethyl vinyl ether, triethoxysilylethyl vinyl ether, trimethoxysilylbutyl vinyl ether, methyldimethoxysilylethyl vinyl ether, trimethoxysilylpropyl vinyl ether, triethoxysilylpropyl vinyl ether, etc.

[0119] In the above-mentioned fluorinated polymer, the total of the polymerization units based on the monomers containing hydroxyl groups (-OH groups) and the polymerization units based on the monomers containing carboxyl groups (-COOH groups) is less than 1 mol% relative to all polymerization units. The total of the polymerization units based on the monomers containing hydroxyl groups (-OH groups) and the polymerization units based on the monomers containing carboxyl groups (-COOH groups) is preferably less than 0.5 mol%, more preferably less than 0.3 mol%, further preferably less than 0.1 mol%, and particularly preferably 0.0 mol%. By making the total of the polymerization units based on the monomers containing hydroxyl groups (-OH groups) and the polymerization units based on the monomers containing carboxyl groups (-COOH groups) be the above range, it is possible to improve low dielectric constant and low dielectric loss tangent.

[0120] Examples of the monomer containing a hydroxyl group (—OH group) include hydroxyalkyl vinyl ether, hydroxyalkyl allyl ether, hydroxycarboxylic acid vinyl ester, hydroxycarboxylic acid allyl ester, and hydroxyalkyl (meth)acrylate.

[0121] Examples of the hydroxyalkyl vinyl ether include 2-hydroxyethyl vinyl ether, 3-hydroxypropyl vinyl ether, 2-hydroxypropyl vinyl ether, 2-hydroxy-2-methylpropyl vinyl ether, 4-hydroxybutyl vinyl ether, 4-hydroxy-2-methylbutyl vinyl ether, 5-hydroxypentyl vinyl ether, and 6-hydroxyhexyl vinyl ether.

[0122] Examples of the hydroxyalkyl allyl ether include 2-hydroxyethyl allyl ether, 4-hydroxybutyl allyl ether, and glycerol monoallyl ether.

[0123] Examples of the hydroxycarboxylic acid vinyl esters include vinyl glycolate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxycaproate, and 4-hydroxycyclohexyl vinyl acetate.

[0124] Examples of the hydroxycarboxylic acid allyl ester include allyl glycolate, allyl hydroxypropionate, allyl hydroxybutyrate, allyl hydroxyhexanoate, and allyl 4-hydroxycyclohexyl acetate.

[0125] Examples of the hydroxyalkyl (meth)acrylate include 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate.

[0126] Examples of the carboxyl group-containing monomer include the following:

[0127] R 1a R 2a C=CR 3a -(CH2) n -COOH(B)

[0128] (Where R 1a , R2a and R 3a The monomers are the same or different and are hydrogen atoms or linear or branched alkyl groups having 1 to 10 carbon atoms; n is an integer greater than 0). Examples thereof include acrylic acid, methacrylic acid, vinylacetic acid, crotonic acid, pentenoic acid, hexenoic acid, heptenoic acid, octenoic acid, nonenoic acid, decenoic acid, undecenoic acid, dodecenoic acid, tridecenoic acid, tetradecenoic acid, pentadecenoic acid, hexadecenoic acid, heptadecenoic acid, octadecenoic acid, nonadecenoic acid, eicosenoic acid, and 2,2-tricosenoic acid.

[0129] Examples of the carboxyl group-containing monomer include cinnamic acid, 3-allyloxypropionic acid, itaconic acid, itaconic acid monoester, maleic acid, maleic acid monoester, maleic anhydride, fumaric acid, fumaric acid monoester, vinyl phthalate, vinyl pyromellitate, citraconic acid, mesaconic acid, and aconitic acid.

[0130] As the above-mentioned other monomers, from the aspect of improving curability, it is preferred to include a monomer containing an epoxy group or a monomer containing an oxetane group. As the above-mentioned monomer containing an epoxy group, allyl glycidyl ether, acrylate-4-hydroxybutyl glycidyl ether, methacrylate 3,4-epoxycyclohexyl methyl ester, etc. can be mentioned. As the above-mentioned monomer containing an oxetane group, acrylic acid (3-ethyloxetane-3-yl) methyl ester, etc. can be mentioned. The content of the monomer containing an epoxy group and an oxetane group is preferably 0.1 mol% or more, more preferably 0.5 mol% or more, and further preferably 1 mol% or more relative to all polymerized units. In addition, it is preferably 15 mol% or less, more preferably 10 mol% or less, and particularly preferably 5 mol% or less.

[0131] As the above-mentioned other monomers not containing a hydroxyl group and a carboxyl group, a monomer containing a heterocyclic ring not containing a hydroxyl group and a carboxyl group is preferred from the aspect of improving adhesion. Examples of the above-mentioned monomer containing a heterocyclic ring include monomers containing a cyclic ether group such as furan, tetrahydrofurfuryl acrylate, and 2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate, monomers containing a lactone group such as 5-oxo-4-oxatricyclo[4.2.1.03.7]nonane-2-yl=acrylate, monomers containing anhydride groups such as itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride, and monomers containing a pyrrolidone group such as N-vinyl-2-pyrrolidone. The content of the monomer containing a heterocyclic ring is preferably 0.1 mol% or more, more preferably 0.5 mol% or more, and further preferably 1 mol% or more relative to the total polymerized units. From the viewpoint of heat resistance, the content is preferably 20 mol % or less, more preferably 10 mol % or less, and particularly preferably 5 mol % or less.

[0132] As the other monomer, it is preferred to include the monomer (2) from the viewpoint of heat resistance, low dielectric constant, and low dielectric loss tangent. B It is H or CH3, preferably H. From the perspective of being able to further improve heat resistance, the polymerized units based on the above-mentioned monomer (2) are preferably 10 mol% or more relative to the total polymerized units. It is more preferably 15 mol% or more, and further preferably 20 mol% or more. In addition, due to the excellent low dielectric constant and low dielectric loss tangent, the above-mentioned monomer (2) units are preferably 90 mol% or less relative to the total polymerized units. It is more preferably 80 mol% or less, further preferably 70 mol% or less, further more preferably 60 mol% or less, and particularly preferably 50 mol% or less.

[0133] In the first fluorinated polymer of the present disclosure, the molar ratio of the fluorinated vinyl monomer unit / the vinyl ester monomer unit is preferably (10-90) / (10-90), more preferably (20-80) / (20-80), further preferably (30-70) / (30-70).

[0134] In the fluorinated polymer, the total content of the fluorinated vinyl monomer units and the vinyl ester monomer units is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, still more preferably 95 mol% or more, and particularly preferably 97 mol% or more relative to the total polymerized units. It can be 100 mol% relative to the total polymerized units.

[0135] The content of the above-mentioned other monomer units is preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less, still more preferably 5 mol% or less, and particularly preferably 3 mol% or less relative to the total polymerized units of the fluorinated polymer. In addition, it is preferably 0 mol% or more, more preferably 0.1 mol% or more, and further preferably 0.5 mol% or more relative to the total polymerized units of the fluorinated polymer.

[0136] In a particularly preferred embodiment of the first fluorinated polymer disclosed herein, the first fluorinated polymer comprises 10 to 90 mol% of TFE units, HFP units or CTFE units, 10 to 80 mol% of monomer units represented by formula (A), 0 to 80 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 10 mol% of other monomer units.

[0137] In a more preferred embodiment, the polyol contains 20 to 80 mol% of TFE units, HFP units or CTFE units, 10 to 70 mol% of monomer units represented by formula (A), 0 to 60 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 10 mol% of other monomer units. In a further preferred embodiment, the polyol contains 30 to 70 mol% of TFE units, HFP units or CTFE units, 20 to 60 mol% of monomer units represented by formula (A), 0 to 40 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 10 mol% of other monomer units. In a particularly preferred embodiment, the polyol contains 35 to 65 mol% of TFE units, HFP units or CTFE units, 25 to 55 mol% of monomer units represented by formula (A), 0 to 35 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 5 mol% of other monomer units.

[0138] A preferred embodiment of the first fluorinated polymer of the present disclosure comprises 10 to 90 mol % of TFE units, HFP units or CTFE units, 10 to 80 mol % of monomer units represented by formula (A), and 1 to 60 mol % of monomer (2) units represented by general formula (2).

[0139] In a more preferred embodiment, the polyol contains 20 to 80 mol% of TFE units, HFP units or CTFE units, 10 to 70 mol% of monomer units represented by formula (A), and 5 to 50 mol% of monomer (2) units represented by general formula (2). In a further preferred embodiment, the polyol contains 30 to 70 mol% of TFE units, HFP units or CTFE units, 20 to 60 mol% of monomer units represented by formula (A), and 10 to 40 mol% of monomer (2) units represented by general formula (2). In a particularly preferred embodiment, the polyol contains 35 to 65 mol% of TFE units, HFP units or CTFE units, 25 to 55 mol% of monomer units represented by formula (A), and 10 to 30 mol% of monomer (2) units represented by general formula (2).

[0140] The first fluorinated polymer of the present disclosure is preferably a compound having a group (hereinafter also referred to as "active ester group (A)") formed by esterifying an OH group with high acidity, specifically an OH group with a pKa of 25 or less (measured value in a dimethyl sulfoxide solvent) with an aromatic acid or a fatty acid (hereinafter also referred to as "active ester group (A)"). By making the fluorinated polymer of the present disclosure the above-mentioned active ester compound (A), it can be a compound that can react with an epoxy resin more effectively.

[0141] For example, fluorinated alcohols are known to be alcohols with high acidity, and their pKa is less than 25 (measured value in dimethyl sulfoxide solvent, the same below). For example, (CH3)3COH, which is a non-fluorinated alcohol, has a pKa of 32.2, while CF3CH2OH has a pKa of 23.5 and (CF3)2CHOH has a pKa of 17.9.

[0142] In contrast, the pKa of a phenolic hydroxyl group is substantially the same as that of a fluorinated alcohol. It is known that the pKa of naphthol is 17.2, and the pKa of 2,6-di-tert-butylphenol is 16.8.

[0143] Furthermore, the first fluorinated polymer of the present disclosure preferably comprises polymerized units based on a monomer having the above-mentioned active ester group (A).

[0144] In the fluorinated polymer of the present disclosure, the polymerized units based on the monomer having the active ester group (A) account for preferably 10 to 70 mol %, more preferably 20 to 60 mol %, further preferably 25 to 55 mol % based on all the polymerized units.

[0145] From the viewpoint of low dielectric constant and low dielectric loss tangent, the fluorine content of the first fluorinated polymer disclosed herein is preferably 20 mass % or more, more preferably 25 mass % or more, further preferably 30 mass % or more, particularly preferably 35 mass % or more.

[0146] The fluorine content of the fluorine-containing polymer can be determined by elemental analysis using an automatic sample combustion apparatus.

[0147] In the first fluorinated polymer of the present disclosure, the vinyl ester monomer unit equivalent is preferably 90 to 5000 g / eg, more preferably 90 to 1000 g / eg, and still more preferably 90 to 500 g / eg.

[0148] The above-mentioned vinyl ester monomer unit equivalent can be calculated based on the composition.

[0149] The number average molecular weight of the first fluorinated polymer disclosed in the present invention is preferably 1000 to 50000. When the number average molecular weight of the fluorinated polymer is within such a range, the reactivity as an active ester is improved, so that it can react effectively with the epoxy resin, and the resin layer of the metal-clad laminate can be firmly bonded to the metal foil. The number average molecular weight of the fluorinated polymer is more preferably 1000 to 30000, more preferably 1000 to 20000, and more preferably 1000 to 15000.

[0150] From the viewpoint of increasing the gel fraction, the number average molecular weight is preferably 10,000 or less, more preferably 7,000 or less, further preferably 5,000 or less, and particularly preferably 3,000 or less.

[0151] The number average molecular weight of the fluorine-containing polymer can be measured by gel permeation chromatography (GPC).

[0152] The glass transition temperature of the first fluorinated polymer disclosed herein is preferably 30° C. or higher, more preferably 40° C. or higher, further preferably 50° C. or higher, still further preferably 60° C. or higher, further preferably 65° C. or higher, particularly further preferably 70° C. or higher, and particularly preferably 100° C. or higher. The higher the glass transition temperature, the better. However, from the viewpoint of processability, it is preferably 200° C. or lower.

[0153] The glass transition temperature is a value determined by a midpoint method based on heat absorption in the second run using a DSC measuring apparatus under the following conditions in accordance with ASTM E1356-98.

[0154] Measurement conditions

[0155] Heating rate: 20℃ / min

[0156] Sample volume: 10 mg

[0157] Thermal cycle: -50℃~150℃, heating, cooling, heating

[0158] In the first fluorinated polymer disclosed herein, the segment (T'V'T' segment) of the fluorinated vinyl monomer unit (T')-vinyl ester monomer unit (V')-fluorinated vinyl monomer unit (T') is preferably 45 mol% or more. By making the T'V'T' segment 45 mol% or more, the gel fraction can be increased. In order to further increase the gel fraction, the T'V'T' segment is preferably 50 mol% or more, more preferably 55 mol% or more, further preferably 60 mol% or more, further more preferably 65 mol% or more, particularly more preferably 70 mol% or more, and particularly preferably 75 mol% or more.

[0159] The above-mentioned T'V'T' segment can be calculated based on the peak area of ​​NMR analysis. For example, when the fluorine-containing vinyl monomer is TFE and the vinyl ester monomer is vinyl benzoate, there is a peak near 6.1ppm in the segment arranged as T'V'T'. Similarly, the T'V'V'T' segment has a peak near 5.9ppm, and the T'V'V'V'T' segment has a peak near 5.6ppm. The proportion of the T'V'T' segment is calculated using the following formula based on the areas of these peaks. The unit is mol%.

[0160] (Ratio of T'V'T' segments) = ((Peak area of ​​T'V'T' segments) / ((Peak area of ​​T'V'T' segments) + (Peak area of ​​T'V'V'T' segments) + (Peak area of ​​T'V'V'V'T' segments))) × 100

[0161] The ratio of T'V'V'T' links and the ratio of T'V'V'V'T' links are calculated in the same manner.

[0162] The fluorine-containing vinyl monomer unit is preferably a polymerization unit based on TFE (TFE unit), and the vinyl ester monomer unit is preferably a polymerization unit based on vinyl benzoate.

[0163] The first fluorinated polymer disclosed in the present invention can be produced by adjusting the composition of the fluorinated polymer as described above.

[0164] The first fluorinated polymer disclosed in the present invention can be produced by solution polymerization, emulsion polymerization, suspension polymerization or bulk polymerization, and among them, a polymer obtained by solution polymerization is preferred.

[0165] The first fluorinated polymer disclosed herein is preferably produced by polymerizing the monomer imparting the above-mentioned unit by a solution polymerization method using an organic solvent, a polymerization initiator, a chain transfer agent, etc., thereby producing the fluorinated polymer. The polymerization temperature is usually 0 to 150° C., preferably 5 to 95° C. The polymerization pressure is usually 0.1 to 10 MPaG (1 to 100 kgf / cm 2 G).

[0166] Examples of the organic solvent include esters such as methyl acetate, ethyl acetate, propyl acetate, n-butyl acetate, and tert-butyl acetate; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; aliphatic hydrocarbons such as hexane, cyclohexane, octane, nonane, decane, undecane, dodecane, and mineral spirits; aromatic hydrocarbons such as benzene, toluene, xylene, naphthalene, and solvent naphtha; alcohols such as methanol, ethanol, tert-butyl alcohol, isopropanol, and ethylene glycol monoalkyl ether; cyclic ethers such as tetrahydrofuran, tetrahydropyran, and dioxane; dimethyl sulfoxide, or mixtures thereof.

[0167] As the above-mentioned polymerization initiator, for example, persulfates such as ammonium persulfate and potassium persulfate can be used (reducing agents such as sodium bisulfite, sodium pyrosulfite, cobalt naphthenate, dimethylaniline, etc. can also be used in combination as needed); redox initiators composed of an oxidizing agent (such as ammonium peroxide, potassium peroxide, etc.), a reducing agent (such as sodium sulfite, etc.) and a transition metal salt (such as iron sulfate, etc.); diacyl peroxides such as acetyl peroxide and benzoyl peroxide; dialkoxycarbonyl peroxides such as isopropoxycarbonyl peroxide and tert-butoxycarbonyl peroxide; ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide; peroxy Hydroperoxides such as hydrogen peroxide, tert-butyl hydroperoxide, and cumene hydroperoxide; dialkyl peroxides such as di-tert-butyl peroxide and dicumyl peroxide; alkyl peroxyesters such as tert-butyl peroxyacetate and tert-butyl peroxypivalate; azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), dimethyl 2,2'-azobisisobutyrate, 2,2'-azobis[2-(hydroxymethyl)propionitrile], and 4,4'-azobis(4-cyanopentenoic acid).

[0168] The chain transfer agent is, for example, an alcohol, preferably an alcohol having 1 to 10 carbon atoms, and more preferably a monohydric alcohol having 1 to 10 carbon atoms. Specifically, methanol, ethanol, propanol, isopropanol, n-butanol, tert-butanol, 2-methylpropanol, cyclohexanol, methylcyclohexanol, cyclopentanol, methylcyclopentanol, and dimethylcyclopentanol can be used. Among them, methanol, isopropanol, tert-butanol, cyclohexanol, methylcyclohexanol, cyclopentanol, and methylcyclopentanol are preferred, and methanol and isopropanol are particularly preferred.

[0169] When producing a fluorinated polymer having a T'V'T' segment of 45 mol % or more, the ratio of the fluorinated vinyl monomer can be increased, the amount of the vinyl ester monomer supplied to the reactor per unit time can be reduced, and the monomer and the solvent can be mixed and introduced into the reactor for simultaneous polymerization.

[0170] The first composition for metal-clad laminates of the present disclosure comprises the first fluorinated polymer of the present disclosure and a solvent.

[0171] In the first metal-clad laminate composition disclosed herein, by making the fluorine-containing polymer have the above-mentioned structure, the compatibility with epoxy resin is excellent. In addition, by being used in the resin layer of the metal-clad laminate, the resin layer can have a low dielectric constant and a low dielectric loss tangent. The present disclosure provides the use of the above-mentioned metal-clad laminate composition in the metal-clad laminate (resin layer of the metal-clad laminate).

[0172] The first composition for metal-clad laminates disclosed herein contains a solvent. As the above-mentioned solvent, an organic solvent is preferably used. The organic solvent is not particularly limited, and examples thereof include esters such as ethyl acetate, butyl acetate, isopropyl acetate, isobutyl acetate, cellosolve acetate, and propylene glycol methyl ether acetate; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; cyclic ethers such as tetrahydrofuran and dioxane; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; aromatic hydrocarbons such as toluene and xylene; alcohols such as propylene glycol methyl ether; hydrocarbons such as hexane and heptane; and mixed solvents thereof.

[0173] The first metal-clad laminate composition disclosed herein may further include a curing accelerator. As the above-mentioned curing accelerator, phosphorus compounds, tertiary amines, imidazole compounds, pyridine compounds, organic acid metal salts, Lewis acids, amine complex salts, etc. can be cited. Preferably, it is a basic catalyst, specifically, more preferably at least one selected from the group consisting of alkali metal hydroxides, pyridines and imidazole compounds. More preferably, it is at least one selected from the group consisting of tertiary amines, imidazole compounds, pyridine compounds and amine complex salts, and further more preferably at least one selected from the group consisting of imidazole compounds and pyridine compounds, particularly preferably 4-dimethylaminopyridine and 2-ethyl-4-methylimidazole.

[0174] These components may be used alone or in combination of two or more.

[0175] In the first composition for metal-clad laminate disclosed herein, the fluorinated polymer preferably accounts for 10% by mass or more, more preferably 25% by mass or more, and further preferably 40% by mass or more, relative to 100% by mass of the solid content. It may be 100% by mass or less, and may be 80% by mass or less.

[0176] The first metal-clad laminate composition of the present disclosure may not contain an epoxy resin.

[0177] The first curable composition disclosed in the present invention comprises a fluorine-containing polymer and an epoxy resin, wherein the fluorine-containing polymer comprises polymerized units based on a fluorine-containing vinyl monomer and polymerized units based on a vinyl ester (excluding the polymerized units based on the fluorine-containing vinyl monomer), and the total amount of polymerized units based on a monomer containing an -OH group and polymerized units based on a monomer containing a -COOH group is 1 mol% or less relative to all polymerized units.

[0178] The compatibility of the fluorine-containing polymers proposed in the resin layers of conventional metal-clad laminates with epoxy resins cannot be said to be sufficient.

[0179] The first curable composition of the present disclosure contains the fluorinated polymer and has excellent compatibility with the epoxy resin, and therefore has a low dielectric constant and a low dielectric loss tangent, and also has excellent dispersibility, moisture resistance, heat resistance, flame retardancy, and adhesiveness.

[0180] In addition, by including the fluorinated polymer, a resin layer having a low dielectric constant and a low dielectric loss tangent can be formed, and thus the resin layer is particularly suitable for forming a resin layer of a metal-clad laminate.

[0181] The first curable composition of the present disclosure is preferably a curable composition for metal-clad laminates. The present disclosure provides use of the curable composition in metal-clad laminates (resin layers of metal-clad laminates).

[0182] In the first curable composition of the present disclosure, the fluorinated polymer is the same as the fluorinated polymer for metal-clad laminates of the present disclosure and the fluorinated polymer in the composition for metal-clad laminates of the present disclosure. Therefore, all preferred embodiments of the fluorinated polymer described in the fluorinated polymer for metal-clad laminates of the present disclosure and the composition for metal-clad laminates can be adopted.

[0183] Examples of the epoxy resin include phenolic novolac epoxy resins, cresol-phenolic novolac epoxy resins, naphthol novolac epoxy resins, bisphenol novolac epoxy resins, biphenolic novolac epoxy resins, bisphenol epoxy resins, biphenyl epoxy resins, trisphenol methane epoxy resins, tetraphenol ethane epoxy resins, dicyclopentadiene-phenol addition reaction epoxy resins, phenol aralkyl epoxy resins, and naphthol aralkyl epoxy resins.

[0184] More specifically, examples include Epikote 828 (manufactured by Shell Chemical Co., Ltd.) of epibis-type compounds based on bisphenol A or the like, alkyl-modified EPICLON 800, EPICLON 4050, EPICLON 1121N (manufactured by DIC Corporation), Shodyne (manufactured by Showa Denko K.K.), Araldite CY-183 (manufactured by Ciba-Geigy Co., Ltd.) and other glycidyl ester compounds, novolac-type Epikote 154 (manufactured by Shell Chemical Co., Ltd.), DEN 431, DEN 438 (manufactured by Dow Chemical Co., Ltd.), cresol novolac-type ECN 1280, ECN 1235 (manufactured by Ciba-Geigy Co., Ltd.), and urethane-modified EPU-6, EPU-10 (manufactured by Dilong Chemical Industry Co., Ltd.).

[0185] The weight average molecular weight of the epoxy resin is preferably 100 to 1,000,000. When the weight average molecular weight of the epoxy resin is within such a range, the resin layer and the metal foil can be firmly bonded. The weight average molecular weight of the epoxy resin is more preferably 1,000 to 100,000.

[0186] The weight average molecular weight of the epoxy resin can be measured by, for example, gel permeation chromatography (GPC).

[0187] The epoxy equivalent of the epoxy resin is preferably 50 to 5000 g / eg, more preferably 50 to 1000 g / eg, and even more preferably 50 to 500 g / eg.

[0188] The epoxy equivalent is determined in accordance with JIS7236.

[0189] In the first curable composition of the present disclosure, the ratio (value obtained by multiplying the mass of the fluorinated polymer by the vinyl ester monomer unit equivalent) / (value obtained by multiplying the mass of the epoxy resin by the epoxy equivalent) is preferably 0.4 to 2.0. It is more preferably 0.5 to 1.5, further preferably 0.7 to 1.3, still more preferably 0.8 to 1.2, and particularly preferably 0.9 to 1.1. By making the above ratio within the above range, the fluorinated polymer and the epoxy resin can be cured efficiently.

[0190] In the first curable composition disclosed herein, from the aspects of dielectric constant, dielectric loss tangent, dispersibility, moisture resistance, heat resistance, flame retardancy, and adhesiveness, the epoxy resin preferably contains 1 part by mass or more, more preferably 50 parts by mass or more, and further preferably 80 parts by mass or more, relative to 100 parts by mass of the fluorinated polymer. In addition, the epoxy resin preferably contains 1000 parts by mass or less, more preferably 500 parts by mass or less, further preferably 300 parts by mass or less, and particularly preferably 200 parts by mass or less, relative to 100 parts by mass of the fluorinated polymer.

[0191] The first curable composition of the present disclosure may contain a flame retardant, an inorganic filler, a silane coupling agent, a release agent, a pigment, an emulsifier, and the like in addition to the epoxy resin.

[0192] The first curable composition of the present disclosure preferably further comprises a curing accelerator. As the above-mentioned curing accelerator, as the above-mentioned curing accelerator, phosphorus compounds, tertiary amines, imidazole compounds, pyridine compounds, organic acid metal salts, Lewis acids, amine complex salts, etc. can be cited. It is preferably a basic catalyst, specifically, more preferably at least one selected from the group consisting of hydroxides of alkali metals, pyridines and imidazole compounds. It is further preferably at least one selected from the group consisting of tertiary amines, imidazole compounds, pyridine compounds and amine complex salts, and further more preferably at least one selected from the group consisting of imidazole compounds and pyridine compounds, particularly preferably 4-dimethylaminopyridine, 2-ethyl-4-methylimidazole.

[0193] These substances may be used alone or in combination of two or more.

[0194] The first curable composition of the present disclosure may contain various additives according to the required properties. Examples of the additives include pigment dispersants, defoamers, leveling agents, UV absorbers, light stabilizers, thickeners, adhesion improvers, matting agents, and the like.

[0195] When the first curable composition of the present disclosure contains the above-mentioned various additives, in the curable composition of the present disclosure, the total amount of the above-mentioned fluorinated polymer and the epoxy resin relative to 100 mass% of the solid content is preferably 5 mass% or more, more preferably 50 mass% or more, further preferably 70 mass% or more, and even more preferably 80 mass% or more.

[0196] The first curable composition of the present disclosure preferably contains an organic solvent. Examples of the organic solvent include esters such as ethyl acetate, butyl acetate, isopropyl acetate, isobutyl acetate, cellosolve acetate, and propylene glycol methyl ether acetate; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; cyclic ethers such as tetrahydrofuran and dioxane; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; aromatic hydrocarbons such as toluene and xylene; alcohols such as propylene glycol methyl ether; hydrocarbons such as hexane and heptane; and mixed solvents thereof.

[0197] The curable composition of the present disclosure preferably has a solid content concentration of 10 to 80% by mass based on the total amount of the fluorinated polymer and the epoxy resin. When the solid content concentration is within this range, the curable composition has an appropriate viscosity and can be applied to form a uniform coating film.

[0198] The method for preparing the first curable composition of the present disclosure is not particularly limited, and examples thereof include a method of mixing a solution or dispersion of a fluorine-containing polymer with a solution or dispersion of an epoxy resin.

[0199] The first curable composition disclosed in the present invention can be used as a resin layer of a metal-clad laminate, and can also be used as a resin for powder coatings or a resin for optical applications.

[0200] The first metal-clad laminate of the present disclosure is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, wherein the resin layer is formed from the curable composition of the present disclosure. The resin layer can be formed by curing the first curable composition of the present disclosure.

[0201] The first metal-clad laminate disclosed in the present invention is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, wherein the resin layer comprises a fluorine-containing polymer and an epoxy resin, the fluorine-containing polymer comprises polymerization units based on a fluorine-containing vinyl monomer, and polymerization units based on a vinyl ester (excluding the polymerization units based on the fluorine-containing vinyl monomer), and the total of polymerization units based on a monomer containing a -OH group and polymerization units based on a monomer containing a -COOH group is less than 1 mol% relative to all polymerization units.

[0202] The first metal-clad laminate disclosed in the present invention comprises a metal foil and a resin layer. The resin layer has excellent insulating properties and functions as a base material of the metal-clad laminate.

[0203] Examples of the metal foil include metal foils made of copper, aluminum, iron, nickel, chromium, molybdenum, tungsten, zinc or alloys thereof, preferably copper foil. In addition, for the purpose of improving the adhesive force, the metal foil may be subjected to a chemical or mechanical surface treatment such as plate walling, nickel plating, copper-zinc alloy plating, or aluminum alkoxide, aluminum chelate, or silane coupling agent.

[0204] In the resin layer, the epoxy resin preferably contains 1 part by mass or more, more preferably 10 parts by mass or more, further preferably 50 parts by mass or more, and particularly preferably 80 parts by mass or more, relative to 100 parts by mass of the fluoropolymer. In addition, the epoxy resin preferably contains 1000 parts by mass or less, more preferably 500 parts by mass or less, further preferably 300 parts by mass or less, and particularly preferably 200 parts by mass or less, relative to 100 parts by mass of the fluoropolymer. If the fluoropolymer is too much, the adhesiveness may be reduced; if the epoxy resin is too much, the insulation, moisture resistance, heat resistance, and flame retardancy may be reduced.

[0205] The resin layer is obtained from the first curable composition of the present disclosure. Since the fluorinated polymer and the epoxy resin are crosslinked, the above ratio is the ratio of the resin portion derived from the epoxy resin to 100 parts by mass of the resin portion derived from the fluorinated polymer.

[0206] The first metal-clad laminate of the present disclosure may further include other layers as long as it includes a metal foil and the resin layer. The metal foil and the resin layer may each be one type or two or more types.

[0207] The first metal-clad laminate of the present disclosure may further include a second resin layer provided on the resin layer (hereinafter referred to as the "first resin layer"). That is, the first metal-clad laminate of the present disclosure may be formed by laminating the metal foil, the first resin layer, and the second resin layer in this order. The first resin layer plays a role as a base material, and also plays a role as an adhesive layer for bonding the metal foil and the second resin layer.

[0208] In addition, in the first metal-clad laminate of the present disclosure, the first resin layer may be provided on a surface of the metal foil different from the surface on which the first resin layer is provided (the surface on the opposite side). That is, the first metal-clad laminate of the present disclosure may be laminated in the order of the first resin layer, the metal foil, and the first resin layer, or in the order of the first resin layer, the metal foil, the first resin layer, and the second resin layer.

[0209] The second resin layer may be made of a resin used in conventional printed circuit boards. The second resin layer is preferably made of at least one resin selected from the group consisting of polyethylene terephthalate and polyimide, and is more preferably made of polyimide from the viewpoint of heat resistance.

[0210] As the first resin layer, a film having a thickness of 1 to 150 μm may be used. When the metal foil and the second adhesive layer are bonded to each other via the first resin layer, the thickness of the first resin layer after drying may be 1 to 100 μm.

[0211] As the second resin layer, a resin film having a thickness of 1 to 150 μm can be used.

[0212] The first metal-clad laminate of the present disclosure can be obtained by a production method including the step of bonding a metal foil and a film composed of an epoxy resin and a fluorine-containing polymer for the first metal-clad laminate of the present disclosure to obtain a metal-clad laminate.

[0213] As the bonding method, a method of laminating a metal foil and a film containing an epoxy resin and the fluorine-containing polymer and then performing thermocompression bonding at 50 to 300° C. using a heating press is suitable.

[0214] The production method may further include the step of molding a composition containing the epoxy resin and the fluorine-containing polymer to obtain a film composed of the epoxy resin and the fluorine-containing polymer.

[0215] As the molding method, melt extrusion molding, solvent casting, spraying and the like can be cited, but there is no particular limitation. The composition comprising the epoxy resin and the above-mentioned fluorine-containing polymer may include an organic solvent, a curing agent, etc., as described below, and may also include a curing accelerator, a pigment dispersant, a defoamer, a leveling agent, a UV absorber, a light stabilizer, a thickener, a close fit improver, a matting agent, etc.

[0216] The first metal-clad laminate of the present disclosure can also be produced by a method including the step of coating a composition containing an epoxy resin and the above-mentioned fluorine-containing polymer on a metal foil to form a first resin layer.

[0217] The manufacturing method may include the following steps: after the step of forming the first resin layer, further bonding a resin film to be the second resin layer on the first resin layer to obtain a metal-clad laminate having a metal foil and first and second resin layers. The resin film may be a film composed of a resin suitable for forming the second resin layer.

[0218] As a method for bonding the resin films, a method of performing thermocompression bonding at 50 to 300° C. using a heating press machine is preferred.

[0219] In the above-mentioned production method, as a method for applying the composition for forming the first resin layer to the metal foil, there can be mentioned brush coating, dip coating, spray coating, comma coating, knife coating, die coating, die lip coating, roll coater coating, curtain coating, etc. After the composition is applied, it can be cured by drying at 25 to 200° C. for 1 minute to 1 week in a hot air drying furnace or the like.

[0220] The first metal-clad laminate of the present disclosure can also be manufactured by a manufacturing method including the following steps: a step of applying the first curable composition of the present disclosure onto a resin film that becomes a second resin layer to form a first resin layer; and a step of bonding a metal foil to the first resin layer of a laminate formed of the first resin layer and the second resin layer obtained by the forming step to obtain a metal-clad laminate having a metal foil and the first and second resin layers. As the above-mentioned resin film, a film composed of a resin suitable for forming the second resin layer can be cited.

[0221] As a method for applying the composition for forming the first resin layer to the resin film, there can be mentioned brush coating, dip coating, spray coating, comma coating, knife coating, die coating, die lip coating, roll coater coating, curtain coating, etc. After the composition is applied, it can be cured by drying at 25 to 200° C. for 1 minute to 1 week in a hot air drying furnace or the like.

[0222] In the above-mentioned manufacturing method, as a method for bonding metal foil to the first resin layer of a laminate formed by a first resin layer and a second resin layer, the following method is preferred: after overlapping the laminate formed by the first resin layer and the second resin layer and the metal foil in a manner such that the first resin layer of the laminate and the metal foil are bonded, hot pressing is performed using a heating press at 50 to 300°C.

[0223] The present disclosure also provides a printed circuit board, characterized in that it has a pattern circuit formed by etching the metal foil of the first metal-clad laminate of the present disclosure. The printed circuit board of the present disclosure may be a flexible substrate or a rigid substrate, preferably a flexible substrate.

[0224] The first printed circuit board of the present disclosure may include a coverlay film on the metal-clad laminate, and the coverlay film may be bonded to the metal-clad laminate via the resin layer.

[0225] The etching method is not limited, and a conventionally known method can be used. In addition, the pattern circuit is not limited, and any pattern circuit printed substrate can be used.

[0226] The use of the first printed circuit board disclosed in the present invention is not limited. For example, since the printed circuit board disclosed in the present invention has a resin layer with a low dielectric constant and a low dielectric loss tangent, it can also be used in printed circuit boards used in applications with high bandwidths such as 4G (37.5Mbps) and 5G (several G to 20Gbps).

[0227] The second fluorine-containing polymer disclosed in the present invention is characterized in that it contains polymerized units based on TFE and polymerized units based on vinyl ester monomers, the chain segments of TFE unit-vinyl ester monomer unit-TFE unit are 45 mol% or more, and the total of polymerized units based on monomers containing hydroxyl groups and polymerized units based on monomers containing carboxyl groups is 1 mol% or less relative to all polymerized units. By having the above-mentioned structure, the second fluorine-containing polymer disclosed in the present invention can be made to have excellent compatibility with epoxy resin and can increase the gel fraction after immersion in acetone.

[0228] In the second fluorinated polymer disclosed herein, the segment (TVT segment) of TFE unit (T)-vinyl ester monomer unit (V)-TFE unit (T) is 45 mol% or more. By making the TVT segment 45 mol% or more, the reactivity with epoxy resin is excellent. For the reason of more excellent reactivity with epoxy resin, in the second fluorinated polymer disclosed herein, the TVT segment is preferably 50 mol% or more, more preferably 55 mol% or more, further preferably 60 mol% or more, still more preferably 65 mol% or more, particularly preferably 70 mol% or more, and particularly preferably 75 mol% or more.

[0229] The TVT segment can be calculated from the peak area of ​​NMR analysis. For example, when the vinyl ester monomer is vinyl benzoate, there is a peak at around 6.1ppm in the segment arranged as TVT. Similarly, the TVVT segment has a peak at around 5.9ppm, and the TVVVT segment has a peak at around 5.6ppm. The ratio of each segment is calculated based on the area of ​​these peaks. When other monomers are used, the ratio of the segment is calculated similarly based on the position of the peak.

[0230] The fluorinated polymer having a TVT segment content of 45 mol % or more can be produced by polymerizing while increasing the proportion of TFE and reducing the amount of vinyl ester monomer supplied to the reactor per unit time.

[0231] The second fluorinated polymer disclosed herein comprises a polymerized unit based on TFE (hereinafter also referred to as a "TFE unit"). For reasons of excellent low dielectric constant and low dielectric loss tangent, the TFE unit is preferably 10 mol% or more, more preferably 20 mol% or more, further preferably 30 mol% or more, still more preferably 40 mol% or more, particularly preferably 50 mol% or more, and preferably 80 mol% or less, more preferably 70 mol% or less, and further preferably 60 mol% or less, relative to all the polymerized units constituting the fluorinated polymer.

[0232] The second fluorine-containing polymer disclosed herein comprises polymerized units based on vinyl ester monomers (excluding fluorine-containing vinyl monomers) (hereinafter referred to as "vinyl ester monomer units"). By comprising the vinyl ester monomer units, active esters can be generated and react with epoxy resins.

[0233] The vinyl ester monomer is the same as that in the first fluorinated polymer of the present disclosure. The monomer represented by formula (A) is particularly preferred, and at least one selected from the group consisting of vinyl benzoate, vinyl p-tert-butylbenzoate, vinyl acetate and vinyl pivalate is particularly preferred, and at least one selected from the group consisting of vinyl benzoate, vinyl p-tert-butylbenzoate and vinyl acetate is more preferred.

[0234] The vinyl ester monomer unit is preferably 10 mol% or more, more preferably 20 mol% or more, based on the total polymerized units of the second fluorinated polymer disclosed herein, for reasons of excellent compatibility and reactivity with epoxy resins. The vinyl ester monomer unit is more preferably 30 mol% or more, still more preferably 40 mol% or more, based on the total polymerized units, and is preferably 80 mol% or less, more preferably 70 mol% or less, and even more preferably 60 mol% or less, for reasons of excellent heat resistance.

[0235] In the second fluorinated polymer disclosed in the present invention, the polymerized units based on the monomer represented by the above formula (A) are preferably 10 to 100 mol% relative to the total 100 mol% of the above vinyl ester monomer units, and the polymerized units based on the vinyl ester monomers other than the monomer represented by the above formula (A) are preferably 0 to 90 mol%. The polymerized units based on the monomer represented by the above formula (A) are more preferably 20 to 90 mol%, further preferably 30 to 80 mol%, further more preferably 35 to 75 mol%, and particularly preferably 40 to 70 mol% relative to the total 100 mol% of the above vinyl ester monomer units. The polymerized units based on the vinyl ester monomers other than the monomer represented by the above formula (A) are more preferably 10 to 80 mol%, further preferably 20 to 70 mol%, further more preferably 25 to 65 mol%, and particularly preferably 30 to 60 mol% relative to the total 100 mol% of the above vinyl ester monomer units.

[0236] From the perspective of being used in metal-clad laminates, excellent heat resistance is required. Therefore, as a vinyl ester monomer other than the monomer represented by the above formula (A), a vinyl ester monomer that can increase the glass transition temperature by crosslinking is preferred. For example, vinyl cinnamate, β-styryl vinyl acrylate, β-furyl vinyl acrylate, p-azidocinnamate vinyl ester, etc. can be mentioned.

[0237] The above-mentioned vinyl ester monomer may not contain a hydroxyl group and a carboxyl group.

[0238] The second fluorinated polymer of the present disclosure may further contain polymerized units (hereinafter referred to as “other monomer units”) based on monomers (hereinafter referred to as “other monomers”) other than TFE and the above-mentioned vinyl ester monomers.

[0239] As the above-mentioned other monomers, similarly to the first fluorinated polymer of the present disclosure, there can be mentioned alkyl vinyl ethers not containing a hydroxyl group, non-fluorinated olefins not containing a halogen atom and a hydroxyl group, amino group-containing monomers not containing an NH group, hydrolyzable silyl group-containing monomers not containing an OH group, epoxy group-containing monomers, oxetane group-containing monomers, heterocyclic ring-containing monomers, (meth)acrylate monomers, etc. As the monomers, all the monomers exemplified in the first fluorinated polymer of the present disclosure can be used.

[0240] As the (meth)acrylate, aromatic esters and alicyclic esters of (meth)acrylic acid are preferred from the viewpoint of being able to increase the glass transition temperature of the polymer, and the following general formula (2) is particularly preferred:

[0241] [Chemistry 5]

[0242]

[0243] (Where XB A monomer (2) represented by H or CH3), phenyl (meth)acrylate. In addition, from the viewpoint of being able to function as an active ester, an aromatic ester of (meth)acrylic acid is preferred, and phenyl (meth)acrylate is preferred.

[0244] In the present disclosure, "(meth)acrylic acid" means methacrylic acid or acrylic acid.

[0245] As the above-mentioned other monomers, from the aspect of curability, it is preferred to include a monomer containing an epoxy group or a monomer containing an oxetane group. As the above-mentioned monomer containing an epoxy group, allyl glycidyl ether, acrylate-4-hydroxybutyl glycidyl ether, methacrylate 3,4-epoxycyclohexyl methyl ester, etc. can be mentioned. As the above-mentioned monomer containing an oxetane group, acrylic acid (3-ethyloxetane-3-yl) methyl ester, etc. can be mentioned. The content of the monomer containing an epoxy group and an oxetane group is preferably 0.1 mol% or more, more preferably 0.5 mol% or more, and further preferably 1 mol% or more relative to all polymerized units. In addition, it is preferably 15 mol% or less, more preferably 10 mol% or less, and particularly preferably 5 mol% or less.

[0246] As the above-mentioned other monomers not containing a hydroxyl group and a carboxyl group, a monomer containing a heterocyclic ring not containing a hydroxyl group and a carboxyl group is preferred from the aspect of improving adhesion. Examples of the above-mentioned monomer containing a heterocyclic ring include monomers containing a cyclic ether group such as bisfuran, tetrahydrofurfuryl acrylate, and 2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate, monomers containing a lactone group such as 5-oxo-4-oxatricyclo[4.2.1.03.7]nonane-2-yl=acrylate, monomers containing anhydride groups such as itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride, and monomers containing a pyrrolidone group such as N-vinyl-2-pyrrolidone. The content of the monomer containing a heterocyclic ring is preferably 0.1 mol% or more, more preferably 0.5 mol% or more, and further preferably 1 mol% or more relative to the total polymerized units. From the viewpoint of heat resistance, the content is preferably 20 mol % or less, more preferably 10 mol % or less, and particularly preferably 5 mol % or less.

[0247] As the other monomer, it is preferred to contain the monomer (2) from the viewpoint of heat resistance. Bis H or CH3, preferably H. From the perspective of being able to further improve heat resistance, the polymerized units based on the above-mentioned monomer (2) are preferably 10 mol% or more relative to all polymerized units. More preferably, it is 15 mol% or more, and even more preferably, it is 20 mol% or more. In addition, the above-mentioned monomer (2) units are preferably 90 mol% or less relative to all polymerized units. More preferably, it is 80 mol% or less, even more preferably, it is 70 mol% or less, even more preferably, it is 60 mol% or less, and particularly preferably, it is 50 mol% or less.

[0248] In the second fluorine-containing polymer disclosed herein, the total amount of the polymerization unit based on the monomer containing a hydroxyl group (-OH group) and the polymerization unit based on the monomer containing a carboxyl group (-COOH group) is less than 1 mol% relative to all the polymerization units. The total amount of the polymerization unit based on the monomer containing a hydroxyl group (-OH group) and the polymerization unit based on the monomer containing a carboxyl group (-COOH group) is preferably less than 0.5 mol%, more preferably less than 0.3 mol%, further preferably less than 0.1 mol%, and particularly preferably 0.0 mol%. By making the total amount of the polymerization unit based on the monomer containing a hydroxyl group (-OH group) and the polymerization unit based on the monomer containing a carboxyl group (-COOH group) be the above range, it is possible to improve low dielectric constant and low dielectric loss tangent.

[0249] The monomer containing a hydroxyl group (—OH group) and the monomer containing a carboxyl group are the same as those in the first fluorinated polymer of the present disclosure.

[0250] In the second fluorinated polymer of the present disclosure, the molar ratio of TFE unit / vinyl ester monomer unit is preferably (10-90) / (10-90), more preferably (20-80) / (20-80), further preferably (30-70) / (30-70).

[0251] In the fluorinated polymer, the total content of the TFE unit and the vinyl ester monomer unit is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, still more preferably 95 mol% or more, and particularly preferably 97 mol% or more relative to the total polymerized units. It may be 100 mol% relative to the total polymerized units.

[0252] The content of the above-mentioned other monomer units is preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less, still more preferably 5 mol% or less, and particularly preferably 3 mol% or less relative to the total polymerized units of the fluorinated polymer. In addition, it is preferably 0 mol% or more, more preferably 0.1 mol% or more, and further preferably 0.5 mol% or more relative to the total polymerized units of the fluorinated polymer.

[0253] In a particularly preferred embodiment of the second fluorinated polymer disclosed herein, the second fluorinated polymer comprises 10 to 90 mol% of TFE units, 10 to 80 mol% of monomer units represented by formula (A), 0 to 80 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 10 mol% of other monomer units.

[0254] In a more preferred embodiment, the polyol contains 20 to 80 mol% of TFE units, 10 to 70 mol% of monomer units represented by formula (A), 0 to 60 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 10 mol% of other monomer units. In a further preferred embodiment, the polyol contains 30 to 70 mol% of TFE units, 20 to 60 mol% of monomer units represented by formula (A), 0 to 40 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 10 mol% of other monomer units. In a particularly preferred embodiment, the polyol contains 35 to 65 mol% of TFE units, 25 to 55 mol% of monomer units represented by formula (A), 0 to 35 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 5 mol% of other monomer units.

[0255] A preferred embodiment of the second fluorinated polymer of the present disclosure comprises 10 to 90 mol % of TFE units, 10 to 80 mol % of monomer units represented by formula (A), and 1 to 60 mol % of monomer (2) units represented by general formula (2).

[0256] In a more preferred embodiment, the monomer unit comprises 20 to 80 mol % of TFE units, 10 to 70 mol % of monomer units represented by formula (A) and 3 to 50 mol % of monomer (2) units represented by general formula (2). In a further preferred embodiment, the monomer unit comprises 30 to 70 mol % of TFE units, 20 to 60 mol % of monomer units represented by formula (A) and 5 to 40 mol % of monomer (2) units represented by general formula (2). In a particularly preferred embodiment, the monomer unit comprises 35 to 65 mol % of TFE units, 25 to 55 mol % of monomer units represented by formula (A) and 10 to 30 mol % of monomer (2) units represented by general formula (2).

[0257] The second fluorinated polymer of the present disclosure is preferably a compound having a group (hereinafter also referred to as "active ester group (A)") formed by esterifying an OH group with high acidity, specifically an OH group with a pKa of 25 or less (measured value in a dimethyl sulfoxide solvent) with an aromatic acid or a fatty acid (hereinafter also referred to as "active ester group (A)"). By making the second fluorinated polymer of the present disclosure the above-mentioned active ester compound (A), it can be a compound that can react with an epoxy resin more effectively.

[0258] The second fluorinated polymer disclosed in the present invention also preferably contains polymerized units based on a monomer having the above-mentioned active ester group (A).

[0259] In the second fluorinated polymer of the present disclosure, the polymerized units based on the monomer having the active ester group (A) preferably account for 10 to 70 mol %, more preferably 20 to 60 mol %, further preferably 25 to 55 mol % of all polymerized units.

[0260] From the perspective of low dielectric constant and low dielectric loss tangent, the fluorine content of the second fluorine-containing polymer disclosed herein is preferably 20% by mass or more. More preferably, it is 25% by mass or more, further preferably 30% by mass or more, and particularly preferably 35% by mass or more. The fluorine content of the fluorine-containing polymer can be determined by elemental analysis using an automatic sample combustion device.

[0261] In the second fluorinated polymer disclosed herein, the vinyl ester monomer unit equivalent is preferably 90 to 5000 g / eg, more preferably 90 to 1000 g / eg, and even more preferably 90 to 700 g / eg. The vinyl ester monomer unit equivalent can be calculated from the composition.

[0262] The number average molecular weight of the second fluorinated polymer disclosed in the present invention is preferably 1000 to 50000. When the number average molecular weight of the fluorinated polymer is within such a range, the reactivity as an active ester is improved, so that it can react effectively with the epoxy resin, and the resin layer of the metal-clad laminate can be firmly bonded to the metal foil. The number average molecular weight of the fluorinated polymer is more preferably 1000 to 30000, more preferably 1000 to 20000, and more preferably 1000 to 15000.

[0263] The number average molecular weight is more preferably 1,000 to 10,000, further preferably 1,000 to 7,000, still more preferably 1,000 to 5,000, particularly preferably 1,000 to 3,000.

[0264] The number average molecular weight of the fluorine-containing polymer can be measured by gel permeation chromatography (GPC).

[0265] The glass transition temperature of the second fluorinated polymer disclosed in the present invention is preferably 0° C. or higher, more preferably 40° C. or higher, further preferably 50° C. or higher, still further preferably 60° C. or higher, further preferably 65° C. or higher, particularly further preferably 70° C. or higher, and particularly preferably 100° C. or higher. The higher the glass transition temperature, the better. However, from the viewpoint of processability, it is preferably 200° C. or lower.

[0266] The second fluorinated polymer of the present disclosure can be produced by the method described in the first fluorinated polymer of the present disclosure.

[0267] The second composition for metal-clad laminates disclosed herein comprises the second fluorinated polymer disclosed herein and a solvent. In the second composition for metal-clad laminates disclosed herein, by making the fluorinated polymer have the above-mentioned structure, the compatibility with epoxy resin is excellent. In addition, by being used in the resin layer of the metal-clad laminate, the resin layer can have a low dielectric constant and a low dielectric loss tangent. The present disclosure provides the use of the above-mentioned composition for metal-clad laminates in metal-clad laminates (resin layer of metal-clad laminates).

[0268] The second metal-clad laminate composition of the present disclosure contains a solvent. The solvent is the same as that in the first metal-clad laminate composition of the present disclosure.

[0269] The second composition for metal-clad laminates of the present disclosure may further include a curing accelerator. The curing accelerator is the same as that in the first composition for metal-clad laminates of the present disclosure. These substances may be used alone or in combination of two or more.

[0270] In the second composition for metal-clad laminate disclosed in the present invention, the above-mentioned fluorine-containing polymer is preferably 10 mass% or more, more preferably 25 mass% or more, and further preferably 40 mass% or more, relative to 100 mass% of the solid content. In addition, it can be 100 mass% or less, or 80 mass% or less.

[0271] The second composition for metal-clad laminates disclosed in the present invention may not contain an epoxy resin.

[0272] The second curable composition of the present disclosure comprises the second fluorinated polymer of the present disclosure and an epoxy resin. The compatibility between the fluorinated polymer and the epoxy resin proposed in the resin layer of the conventional metal-clad laminate is not yet sufficient.

[0273] The second curable composition of the present disclosure contains the second fluorinated polymer of the present disclosure, and has excellent compatibility with epoxy resin, and therefore has a low dielectric constant and a low dielectric loss tangent, and also has excellent dispersibility, moisture resistance, heat resistance, flame retardancy, and adhesiveness.

[0274] In addition, by including the second fluorinated polymer disclosed herein, a resin layer having a low dielectric constant and a low dielectric loss tangent can be formed, and thus the resin layer is particularly suitable for forming a resin layer of a metal-clad laminate.

[0275] The second curable composition of the present disclosure is preferably a curable composition for metal-clad laminates. The present disclosure provides use of the curable composition in metal-clad laminates (resin layers of metal-clad laminates).

[0276] In the second curable composition of the present disclosure, the epoxy resin is the same as that in the first curable composition of the present disclosure, and all the aspects described in the first curable composition can be adopted.

[0277] In the second curable composition of the present disclosure, the ratio (value obtained by multiplying the mass of the fluorinated polymer by the vinyl ester monomer unit equivalent) / (value obtained by multiplying the mass of the epoxy resin by the epoxy equivalent) is preferably 0.4 to 2.0. It is more preferably 0.5 to 1.5, further preferably 0.7 to 1.3, still more preferably 0.8 to 1.2, and particularly preferably 0.9 to 1.1. By making the above ratio within the above range, the fluorinated polymer and the epoxy resin can be cured efficiently.

[0278] In the second curable composition disclosed herein, from the aspects of dielectric constant, dielectric loss tangent, dispersibility, moisture resistance, heat resistance, flame retardancy, and adhesiveness, the epoxy resin preferably contains 1 part by mass or more, more preferably 50 parts by mass or more, and further preferably 80 parts by mass or more, relative to 100 parts by mass of the fluorinated polymer. In addition, the epoxy resin preferably contains 1000 parts by mass or less, more preferably 500 parts by mass or less, further preferably 300 parts by mass or less, and particularly preferably 200 parts by mass or less, relative to 100 parts by mass of the fluorinated polymer.

[0279] The second curable composition of the present disclosure may contain a flame retardant, an inorganic filler, a silane coupling agent, a release agent, a pigment, an emulsifier, and the like in addition to the epoxy resin.

[0280] The second curable composition of the present disclosure preferably further comprises a curing accelerator. The curing accelerator is the same as that in the first curable composition of the present disclosure. These substances may be used alone or in combination of two or more.

[0281] The second curable composition of the present disclosure may contain various additives according to the required properties. Examples of the additives include pigment dispersants, defoamers, leveling agents, UV absorbers, light stabilizers, thickeners, adhesion improvers, matting agents, and the like.

[0282] When the second curable composition of the present disclosure contains the above-mentioned various additives, in the second curable composition of the present disclosure, the total amount of the second fluorinated polymer of the present disclosure and the epoxy resin relative to 100 mass% of the solid content is preferably 5 mass% or more, more preferably 50 mass% or more, further preferably 70 mass% or more, and even more preferably 80 mass% or more.

[0283] The second curable composition of the present disclosure preferably contains an organic solvent. As an organic solvent, it is the same as in the first curable composition of the present disclosure. In the second curable composition of the present disclosure, the solid content concentration is preferably 10 to 80% by mass based on the total amount of the second fluorinated polymer and the epoxy resin of the present disclosure. When the solid content concentration is within this range, the viscosity of the curable composition is appropriate and can be applied to form a uniform coating film.

[0284] The method for preparing the second curable composition of the present disclosure is not particularly limited, and examples thereof include a method of mixing a solution or dispersion of a fluorine-containing polymer with a solution or dispersion of an epoxy resin.

[0285] The second curable composition disclosed in the present invention can be used as a resin layer of a metal-clad laminate, and can also be used as a resin for powder coatings or a resin for optical applications.

[0286] The second metal-clad laminate of the present disclosure is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, wherein the resin layer is formed from the second curable composition of the present disclosure. The resin layer can be formed by curing the second curable composition of the present disclosure.

[0287] The second metal-clad laminate disclosed in the present invention is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, wherein the resin layer comprises a fluorinated polymer and an epoxy resin, wherein the fluorinated polymer comprises a polymerization unit based on TFE and a polymerization unit based on a vinyl ester monomer, wherein the chain segment of the TFE unit-vinyl ester monomer unit-TFE unit is 45 mol% or more, and the total of the polymerization units based on the monomer containing a hydroxyl group and the polymerization units based on the monomer containing a carboxyl group is 1 mol% or less relative to all the polymerization units.

[0288] The second metal-clad laminate of the present disclosure comprises a metal foil and a resin layer. The resin layer has excellent insulation properties and functions as a base material of the metal-clad laminate.

[0289] The metal foil is the same as that in the first metal-clad laminate of the present disclosure.

[0290] In the resin layer, the epoxy resin preferably contains 1 part by mass or more, more preferably 10 parts by mass or more, further preferably 50 parts by mass or more, and particularly preferably 80 parts by mass or more, relative to 100 parts by mass of the second fluorinated polymer disclosed herein. In addition, the epoxy resin preferably contains 1000 parts by mass or less, more preferably 500 parts by mass or less, further preferably 300 parts by mass or less, and particularly preferably 200 parts by mass or less, relative to 100 parts by mass of the fluorinated polymer. If there is too much fluorinated polymer, the adhesiveness may be reduced; if there is too much epoxy resin, the insulation, moisture resistance, heat resistance, and flame retardancy may be reduced.

[0291] The resin layer is obtained from the second curable composition of the present disclosure. Since the fluorinated polymer and the epoxy resin are crosslinked, the above ratio is the ratio of the resin portion derived from the epoxy resin to 100 parts by mass of the resin portion derived from the fluorinated polymer.

[0292] The second metal-clad laminate of the present disclosure may further include other layers as long as it includes the metal foil and the resin layer. The metal foil and the resin layer may each be one type or two or more types.

[0293] The second metal-clad laminate of the present disclosure may further include a second resin layer provided on the above-mentioned resin layer (hereinafter referred to as "first resin layer"). That is, the second metal-clad laminate of the present disclosure may be formed by laminating the metal foil, the first resin layer and the second resin layer in sequence. The first resin layer plays a role as a base material, and also plays a role as an adhesive layer for bonding the metal foil and the second resin layer.

[0294] In addition, in the second metal-clad laminate of the present disclosure, the first resin layer may be provided on a surface of the metal foil different from the surface on which the first resin layer is provided (the surface on the opposite side). That is, the second metal-clad laminate of the present disclosure may be laminated in the order of the first resin layer, the metal foil, and the first resin layer, or in the order of the first resin layer, the metal foil, the first resin layer, and the second resin layer.

[0295] The second resin layer may be made of a resin used in conventional printed circuit boards. The second resin layer is preferably made of at least one resin selected from the group consisting of polyethylene terephthalate and polyimide, and is more preferably made of polyimide from the viewpoint of heat resistance.

[0296] As the first resin layer, a film having a thickness of 1 to 150 μm may be used. When the metal foil and the second adhesive layer are bonded to each other via the first resin layer, the thickness of the first resin layer after drying may be 1 to 100 μm.

[0297] As the second resin layer, a resin film having a thickness of 1 to 150 μm can be used.

[0298] The second metal-clad laminate of the present disclosure can be produced by the same method as the first metal-clad laminate of the present disclosure, except that the second fluorine-containing polymer of the present disclosure is used as the fluorine-containing polymer.

[0299] The present disclosure also provides a printed circuit board (the second printed circuit board of the present disclosure), characterized in that it has a pattern circuit formed by etching the metal foil of the second metal-clad laminate of the present disclosure. The second printed circuit board of the present disclosure can be a flexible substrate or a rigid substrate, preferably a flexible substrate.

[0300] The second printed circuit board of the present disclosure may include a coverlay film on the metal-clad laminate, and the coverlay film may be bonded to the metal-clad laminate via the resin layer.

[0301] The etching method is not limited, and a conventionally known method can be used. In addition, the pattern circuit is not limited, and any pattern circuit printed substrate can be used.

[0302] The second printed circuit board of the present disclosure is not limited in its use. For example, since the second printed circuit board of the present disclosure has a resin layer with a low dielectric constant and a low dielectric loss tangent, it can also be used in printed circuit boards used for applications with high bandwidths such as 4G (37.5Mbps) and 5G (several G to 20Gbps).

[0303] The third fluorine-containing polymer disclosed in the present invention is characterized in that it contains polymerized units based on a fluorine-containing vinyl monomer and polymerized units based on a vinyl ester monomer, the total content of the polymerized units based on the fluorine-containing vinyl monomer and the polymerized units based on the vinyl ester monomer is 70 to 100 mol% relative to all the polymerized units, the fluorine-containing vinyl monomer contains at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene and chlorotrifluoroethylene, and when the fluorine-containing vinyl monomer contains tetrafluoroethylene, the integral value of CF2H at the terminal of -CF2H in 19F-NMR relative to the integral value of the entire CF2 is 2% or less, when the fluorine-containing vinyl monomer contains hexafluoropropylene, the integral value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR relative to the integral value of the entire CF is 2% or less, and when the fluorine-containing vinyl monomer contains chlorotrifluoroethylene, the total integral value of CF2H at the terminal of -CF2H and the integral value of CFClH at the terminal of -CFClH in 19F-NMR relative to the total integral value of CF2 and the integral value of CFCl is 2% or less. The third fluorinated polymer of the present disclosure can reduce the dielectric loss tangent by having the above-mentioned configuration.

[0304] The third fluorinated polymer of the present disclosure comprises polymerized units based on a fluorinated vinyl monomer (hereinafter referred to as “fluorinated vinyl monomer units”).

[0305] The fluorine-containing vinyl monomer includes at least one selected from the group consisting of tetrafluoroethylene [TFE], hexafluoropropylene [HFP] and chlorotrifluoroethylene [CTFE]. From the perspective of not containing chlorine, at least one selected from the group consisting of TFE and HFP is preferred, and from the perspective of excellent copolymerizability, TFE is particularly preferred.

[0306] For the reasons of excellent low dielectric constant and low dielectric loss tangent, the above-mentioned fluorine-containing vinyl monomer unit is preferably 10 mol% or more, more preferably 20 mol% or more, further preferably 30 mol% or more, still more preferably 40 mol% or more, and particularly preferably 50 mol% or more relative to all the polymerized units constituting the third fluorine-containing polymer disclosed herein. In addition, it is preferably 80 mol% or less, more preferably 70 mol% or less, and further preferably 60 mol% or less.

[0307] When the fluorinated vinyl monomer includes TFE, the integral value of CF2H at the -CF2H terminal in 19F-NMR is 2% or less relative to the integral value of CF2 as a whole. Thus, by reducing the proportion of -CF2H terminals, the dielectric loss tangent can be reduced. For the reason that low dielectric loss tangent is more excellent, the integral value of CF2H at the -CF2H terminal in 19F-NMR is preferably 1% or less, more preferably 0.5% or less relative to the integral value of CF2 as a whole.

[0308] When the fluorinated vinyl monomer includes HFP, the integral value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR is 2% or less relative to the integral value of CF as a whole. Thus, by reducing the proportion of -CF2CFHCF3 terminals, the dielectric loss tangent can be reduced. For the reason that low dielectric loss tangent is more excellent, the integral value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR is preferably 1% or less, more preferably 0.5% or less relative to the integral value of CF as a whole.

[0309] When the above-mentioned fluorine-containing vinyl monomer includes CTFE, the total of the integral value of CF2H at the end of -CF2H in 19F-NMR and the integral value of CFClH at the end of -CFClH relative to the total integral value of CF2 as a whole and the integral value of CFCl as a whole is 2% or less. In this way, by reducing the ratio of -CF2H end and -CFClH end, the dielectric loss tangent can be reduced. For the reason that the low dielectric loss tangent is more excellent, the total of the integral value of CF2H at the end of -CF2H in 19F-NMR and the integral value of CFClH at the end of -CFClH relative to the total integral value of CF2 as a whole and the integral value of CFCl as a whole is preferably 1% or less, more preferably 0.5% or less.

[0310] It should be noted that the measurement method of 19F-NMR and the calculation method of the integral value are not particularly limited, and can be carried out by a common method.

[0311] The ratio of -CF2H terminus, -CF2CFHCF3 terminus, and -CFClH terminus can be reduced, for example, by the following method.

[0312] (Method 1) Polymerization is carried out using a fluorinated solvent.

[0313] (Method 2) Avoid using monomers with high chain transfer properties.

[0314] (Method 3) Adjusting the polymer composition.

[0315] (Method 4) The molecular weight of the polymer is increased.

[0316] Regarding the above-mentioned method 1, the fluorine-based solvent is not particularly limited as long as it is a solvent having fluorine, and examples thereof include fluorinated alkanes, fluorinated aromatic compounds, hydrofluoroethers, fluorinated alkylamines, and fluorinated alcohols.

[0317] As the fluoroalkane, a compound having 4 to 8 carbon atoms is preferred. Examples of commercially available products include C6F 13 H (Asahiklin (registered trademark) AC-2000, manufactured by Asahi Glass Co., Ltd.), C6F 13 C2H5 (Asahiklin (registered trademark) AC-6000 manufactured by Asahi Glass Co., Ltd.), C2F5CHFCHFCF3 (Vertrel (registered trademark) XF manufactured by Chemours Co., Ltd.), and the like.

[0318] Examples of the fluorinated aromatic compound include hexafluorobenzene, trifluoromethylbenzene, perfluorotoluene, and bis(trifluoromethyl)benzene.

[0319] As the hydrofluoroether, a compound having 4 to 12 carbon atoms is preferred. Examples of commercially available products include CF3CH2OCF2CF2H (manufactured by Asahi Glass Co., Ltd., Asahiklin (registered trademark) AE-3000), C4F9OCH3 (manufactured by 3M, Novec (registered trademark) 7100), C4F9OC2H5 (manufactured by 3M, Novec (registered trademark) 7200), and C2F5CF(OCH3)C3F7 (manufactured by 3M, Novec (registered trademark) 7300).

[0320] Examples of the fluoroalkylamine include perfluorotripropylamine and perfluorotributylamine.

[0321] Examples of the fluoroalcohol include 2,2,3,3-tetrafluoropropanol, 2,2,2-trifluoroethanol, hexafluoroisopropanol, etc. Among them, at least one selected from the group consisting of fluoroalkanes, hydrofluoroethers and fluoroalcohols is preferred, and hydrofluoroethers are more preferred.

[0322] Regarding the above-mentioned method 2, examples of monomers having high chain transfer properties include vinyl ethers, allyl ethers, and more specifically, alkyl vinyl ethers, hydroxyalkyl vinyl ethers, alkyl allyl ethers, hydroxyalkyl allyl ethers, vinyl ethers containing other functional groups, and allyl ethers.

[0323] Examples of the vinyl ether include methyl vinyl ether, ethyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, 4-hydroxybutyl vinyl ether, stearyl vinyl ether, chloromethyl vinyl ether, 2-chloroethyl vinyl ether, chloropropyl vinyl ether, cyclohexyl vinyl ether, ethylene glycol monovinyl ether, and diethylene glycol monovinyl ether.

[0324] Examples of the allyl ether include allyl ethyl ether, diallyl ether, and 1,3-diallyloxy-2-propanol.

[0325] Examples of the hydroxyalkyl vinyl ether include 2-hydroxyethyl vinyl ether, 3-hydroxypropyl vinyl ether, 2-hydroxypropyl vinyl ether, 2-hydroxy-2-methylpropyl vinyl ether, 4-hydroxybutyl vinyl ether, 4-hydroxy-2-methylbutyl vinyl ether, 5-hydroxypentyl vinyl ether and 6-hydroxyhexyl vinyl ether.

[0326] Examples of the hydroxyalkyl allyl ether include 2-hydroxyethyl allyl ether, 4-hydroxybutyl allyl ether, glycerol monoallyl ether, etc. Examples of allyl ethers containing other functional groups include allyl glycidyl ether [AGE] having an epoxy group, etc.

[0327] The content of polymerized units based on a monomer having high chain transfer properties is preferably 10 mol% or less, more preferably 5 mol% or less, further preferably 1 mol% or less, based on all polymerized units constituting the third fluorinated polymer of the present disclosure, and may be 0 mol%.

[0328] Regarding the above-mentioned method 3, as an example of adjusting the polymer composition, reducing the fluorine-containing vinyl monomer unit can be cited. From such an aspect, the fluorine-containing vinyl monomer unit is preferably 60 mol% or less, more preferably 50 mol% or less, further preferably 40 mol% or less, and particularly preferably 30 mol% or less relative to all the polymerized units constituting the third fluorine-containing polymer of the present disclosure.

[0329] As another example of adjusting the polymer composition, polymerization can be performed under the condition that residual monomers are present appropriately. As a condition that residual monomers are present appropriately, for example, shortening the time of the aging step (aging reaction) of performing the polymerization reaction at a predetermined temperature after adding the monomers can be mentioned. The time of the aging step is preferably 60 minutes or less, more preferably 30 minutes or less, further preferably 15 minutes or less, and particularly preferably 0 minutes, that is, no aging reaction is performed.

[0330] Regarding the above-mentioned method 4, from the aspect of reducing the ratio of -CF2H terminal, -CF2CFHCF3 terminal, and -CFClH terminal, the number average molecular weight of the third fluorinated polymer disclosed in the present invention is preferably 1000 or more, more preferably 5000 or more, further preferably 7000 or more, still more preferably 9000 or more, and particularly preferably 10000 or more. In addition, from the aspect of reactivity as an active ester, it is preferably 600000 or less, more preferably 100000 or less, further preferably 40000 or less, and particularly preferably 30000 or less.

[0331] The number average molecular weight of the fluorine-containing polymer can be measured by gel permeation chromatography (GPC).

[0332] The third fluorine-containing polymer disclosed herein comprises polymerized units based on vinyl ester monomers (excluding fluorine-containing vinyl monomers) (hereinafter referred to as "vinyl ester monomer units"). By comprising the vinyl ester monomer units, active esters can be generated and react with epoxy resins.

[0333] The vinyl ester monomer is the same as that in the first fluorinated polymer of the present disclosure. The monomer represented by formula (A) is particularly preferred, and at least one selected from the group consisting of vinyl benzoate, vinyl p-tert-butylbenzoate, vinyl acetate and vinyl pivalate is particularly preferred, and at least one selected from the group consisting of vinyl benzoate, vinyl p-tert-butylbenzoate and vinyl acetate is more preferred.

[0334] The vinyl ester monomer unit is preferably 10 mol% or more, more preferably 20 mol% or more, further preferably 30 mol% or more, still more preferably 40 mol% or more, and particularly preferably 50 mol% or more, based on the total polymerized units of the third fluorinated polymer disclosed herein, for reasons of excellent compatibility and reactivity with epoxy resins. In addition, it is preferably 80 mol% or less, more preferably 70 mol% or less, and further preferably 60 mol% or less, for reasons of excellent heat resistance.

[0335] In the third fluorine-containing polymer disclosed in the present invention, the polymerized units based on the monomer represented by the above formula (A) are preferably 10 to 100 mol% relative to the total 100 mol% of the above vinyl ester monomer units, and the polymerized units based on the vinyl ester monomers other than the monomer represented by the above formula (A) are 0 to 90 mol% is one of the preferred embodiments. The polymerized units based on the monomer represented by the above formula (A) are more preferably 20 to 90 mol%, further preferably 30 to 80 mol%, further more preferably 35 to 75 mol%, and particularly preferably 40 to 70 mol% relative to the total 100 mol% of the above vinyl ester monomer units. The polymerized units based on the vinyl ester monomers other than the monomer represented by the above formula (A) are more preferably 10 to 80 mol%, further preferably 20 to 70 mol%, further more preferably 25 to 65 mol%, and particularly preferably 30 to 60 mol% relative to the total 100 mol% of the above vinyl ester monomer units.

[0336] From the perspective of being used in metal-clad laminates, excellent heat resistance is required. Therefore, as a vinyl ester monomer other than the monomer represented by the above formula (A), a vinyl ester monomer that can increase the glass transition temperature by crosslinking is preferred. For example, vinyl cinnamate, β-styryl vinyl acrylate, β-furyl vinyl acrylate, p-azidocinnamate vinyl ester, etc. can be mentioned.

[0337] The above-mentioned vinyl ester monomer may not contain a hydroxyl group and a carboxyl group.

[0338] The third fluorinated polymer of the present disclosure may further contain polymerized units (hereinafter referred to as “other monomer units”) based on monomers (hereinafter referred to as “other monomers”) other than the above-mentioned fluorinated vinyl monomer and the above-mentioned vinyl ester monomer.

[0339] As the above-mentioned other monomers, similarly to the first fluorinated polymer of the present disclosure, there can be mentioned alkyl vinyl ethers not containing a hydroxyl group, non-fluorinated olefins not containing a halogen atom and a hydroxyl group, amino group-containing monomers not containing an NH group, hydrolyzable silyl group-containing monomers not containing an OH group, epoxy group-containing monomers, oxetane group-containing monomers, heterocyclic ring-containing monomers, (meth)acrylate monomers, etc. As the monomers, all the monomers exemplified in the first fluorinated polymer of the present disclosure can be used.

[0340] As the (meth)acrylate, alicyclic esters are preferred from the viewpoint of being able to increase the glass transition temperature of the polymer, and the following general formula (2) is particularly preferred:

[0341] [Chemistry 6]

[0342]

[0343] (Where X BA monomer (2) represented by H or CH3), phenyl (meth)acrylate. In addition, from the viewpoint of being able to function as an active ester, an aromatic ester of (meth)acrylic acid is preferred, and phenyl (meth)acrylate is preferred.

[0344] In the present disclosure, "(meth)acrylic acid" means methacrylic acid or acrylic acid.

[0345] As the above-mentioned other monomers, from the aspect of curability, it is preferred to include a monomer containing an epoxy group or a monomer containing an oxetane group. As the above-mentioned monomer containing an epoxy group, allyl glycidyl ether, acrylate-4-hydroxybutyl glycidyl ether, methacrylate 3,4-epoxycyclohexyl methyl ester, etc. can be mentioned. As the above-mentioned monomer containing an oxetane group, acrylic acid (3-ethyloxetane-3-yl) methyl ester, etc. can be mentioned. The content of the monomer containing an epoxy group and an oxetane group is preferably 0.1 mol% or more, more preferably 0.5 mol% or more, and further preferably 1 mol% or more relative to all polymerized units. In addition, it is preferably 15 mol% or less, more preferably 10 mol% or less, and particularly preferably 5 mol% or less.

[0346] As the above-mentioned other monomers not containing a hydroxyl group and a carboxyl group, a monomer containing a heterocyclic ring not containing a hydroxyl group and a carboxyl group is preferred from the aspect of improving adhesion. Examples of the above-mentioned monomer containing a heterocyclic ring include monomers containing a cyclic ether group such as bisfuran, tetrahydrofurfuryl acrylate, and 2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate, monomers containing a lactone group such as 5-oxo-4-oxatricyclo[4.2.1.03.7]nonane-2-yl=acrylate, monomers containing anhydride groups such as itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride, and monomers containing a pyrrolidone group such as N-vinyl-2-pyrrolidone. The content of the monomer containing a heterocyclic ring is preferably 0.1 mol% or more, more preferably 0.5 mol% or more, and further preferably 1 mol% or more relative to the total polymerized units. From the viewpoint of heat resistance, the content is preferably 20 mol % or less, more preferably 10 mol % or less, and particularly preferably 5 mol % or less.

[0347] As the other monomer, it is preferred to contain the monomer (2) from the viewpoint of heat resistance. Bis H or CH3, preferably H. From the perspective of being able to further improve heat resistance, the polymerized units based on the above-mentioned monomer (2) are preferably 10 mol% or more relative to all polymerized units. More preferably, it is 15 mol% or more, and even more preferably, it is 20 mol% or more. In addition, the above-mentioned monomer (2) units are preferably 90 mol% or less relative to all polymerized units. More preferably, it is 80 mol% or less, even more preferably, it is 70 mol% or less, even more preferably, it is 60 mol% or less, and particularly preferably, it is 50 mol% or less.

[0348] In the third fluorine-containing polymer disclosed herein, the total amount of the polymerization unit based on the monomer containing a hydroxyl group (-OH group) and the polymerization unit based on the monomer containing a carboxyl group (-COOH group) is less than 1 mol% relative to all the polymerization units. The total amount of the polymerization unit based on the monomer containing a hydroxyl group (-OH group) and the polymerization unit based on the monomer containing a carboxyl group (-COOH group) is preferably less than 0.5 mol%, more preferably less than 0.3 mol%, further preferably less than 0.1 mol%, and particularly preferably 0.0 mol%. By making the total amount of the polymerization unit based on the monomer containing a hydroxyl group (-OH group) and the polymerization unit based on the monomer containing a carboxyl group (-COOH group) the above range, it is possible to improve low dielectric constant and low dielectric loss tangent.

[0349] The monomer containing a hydroxyl group (—OH group) and the monomer containing a carboxyl group are the same as those in the first fluorinated polymer of the present disclosure.

[0350] In the third fluorinated polymer of the present disclosure, the molar ratio of the fluorinated vinyl monomer unit / the vinyl ester monomer unit is preferably (10-90) / (10-90), more preferably (20-80) / (20-80), further preferably (30-70) / (30-70).

[0351] In the third fluorinated polymer disclosed herein, the total content of the fluorinated vinyl monomer unit and the vinyl ester monomer unit is 70 to 100 mol% relative to the total polymerized units of the fluorinated polymer. For reasons of excellent low dielectric constant and low dielectric loss tangent, it is preferably 80 to 100 mol%, more preferably 90 to 100 mol%, further preferably 95 to 100 mol%, and particularly preferably 97 to 100 mol%.

[0352] In the third fluorinated polymer disclosed herein, the dielectric loss tangent can be further reduced by reducing the polymerized units based on the monomer containing a hydroxyl group (-OH group). From such an aspect, in the third fluorinated polymer disclosed herein, the polymerized units based on the monomer containing a hydroxyl group are preferably 10 mol% or less, more preferably 5 mol% or less, further preferably 1 mol% or less, and particularly preferably 0 mol%, that is, there are no polymerized units based on the monomer containing a hydroxyl group relative to all polymerized units.

[0353] In addition, as a monomer containing a hydroxyl group, the monomer containing a hydroxyl group exemplified in the description of the 1st fluorine-containing polymer of this disclosure can be mentioned.

[0354] A preferred embodiment of the third fluorinated polymer disclosed herein comprises 10 to 90 mol% of TFE units, HFP units or CTFE units, 10 to 80 mol% of monomer units represented by formula (A), 0 to 80 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 10 mol% of other monomer units.

[0355] In a more preferred embodiment, the polyol contains 20 to 80 mol% of TFE units, HFP units or CTFE units, 10 to 70 mol% of monomer units represented by formula (A), 0 to 60 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 10 mol% of other monomer units. In a further preferred embodiment, the polyol contains 30 to 70 mol% of TFE units, HFP units or CTFE units, 20 to 60 mol% of monomer units represented by formula (A), 0 to 40 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 10 mol% of other monomer units. In a particularly preferred embodiment, the polyol contains 35 to 65 mol% of TFE units, HFP units or CTFE units, 25 to 55 mol% of monomer units represented by formula (A), 0 to 35 mol% of vinyl ester monomer units other than the monomer represented by formula (A), and 0 to 5 mol% of other monomer units.

[0356] A preferred embodiment of the third fluorinated polymer of the present disclosure comprises 10 to 90 mol % of TFE units, HFP units or CTFE units, 10 to 80 mol % of monomer units represented by formula (A), and 1 to 60 mol % of monomer (2) units represented by general formula (2).

[0357] In a more preferred embodiment, the polyol contains 20 to 80 mol% of TFE units, HFP units or CTFE units, 10 to 70 mol% of monomer units represented by formula (A), and 5 to 50 mol% of monomer (2) units represented by general formula (2). In a further preferred embodiment, the polyol contains 30 to 70 mol% of TFE units, HFP units or CTFE units, 20 to 60 mol% of monomer units represented by formula (A), and 10 to 40 mol% of monomer (2) units represented by general formula (2). In a particularly preferred embodiment, the polyol contains 35 to 65 mol% of TFE units, HFP units or CTFE units, 25 to 55 mol% of monomer units represented by formula (A), and 10 to 30 mol% of monomer (2) units represented by general formula (2).

[0358] The third fluorinated polymer of the present disclosure is preferably a compound having a group (hereinafter also referred to as "active ester group (A)") formed by esterifying an OH group with high acidity, specifically an OH group with a pKa of 25 or less (measured value in a dimethyl sulfoxide solvent) with an aromatic acid or a fatty acid (hereinafter also referred to as "active ester group (A)"). By making the second fluorinated polymer of the present disclosure the above-mentioned active ester compound (A), it can be a compound that can react more effectively with an epoxy resin.

[0359] The second fluorinated polymer disclosed in the present invention also preferably contains polymerized units based on a monomer having the above-mentioned active ester group (A).

[0360] In the second fluorinated polymer of the present disclosure, the polymerized units based on the monomer having the active ester group (A) preferably account for 10 to 70 mol %, more preferably 20 to 60 mol %, further preferably 25 to 55 mol % of all polymerized units.

[0361] From the perspective of low dielectric constant and low dielectric loss tangent, the fluorine content of the third fluorine-containing polymer disclosed herein is preferably 20% by mass or more. More preferably, it is 25% by mass or more, further preferably, it is 30% by mass or more, and particularly preferably, it is 35% by mass or more. The fluorine content of the above-mentioned fluorine-containing polymer can be obtained by elemental analysis using an automatic sample combustion device.

[0362] In the third fluorinated polymer disclosed herein, the vinyl ester monomer unit equivalent is preferably 90 to 5000 g / eg, more preferably 90 to 1000 g / eg, and even more preferably 90 to 700 g / eg. The vinyl ester monomer unit equivalent can be calculated from the composition.

[0363] The glass transition temperature of the third fluorine-containing polymer disclosed in the present invention is preferably 0° C. or higher, more preferably 40° C. or higher, further preferably 50° C. or higher, still more preferably 60° C. or higher, further preferably 65° C. or higher, particularly further preferably 70° C. or higher, and particularly preferably 100° C. or higher. The higher the glass transition temperature, the better. However, from the viewpoint of processability, it is preferably 200° C. or lower.

[0364] The dielectric constant of the third fluorinated polymer disclosed in the present invention at 12 GHz is preferably 3.0 or less, more preferably 2.8 or less, and further preferably 2.6 or less. The smaller the dielectric constant, the better. Considering the balance with other physical properties, it may be 0.5 or more, 1 or more, or 2 or more.

[0365] The dielectric loss tangent of the third fluorinated polymer disclosed in the present invention at 12 GHz is preferably 0.013 or less, more preferably 0.012 or less, further preferably 0.010 or less, still more preferably 0.008 or less, and particularly preferably 0.005 or less. The smaller the dielectric loss tangent, the better. Considering the balance with other physical properties, it may be 0.0001 or more, 0.001 or more, 0.002 or more, or 0.004 or more.

[0366] The third fluorinated polymer of the present disclosure can be produced by the same method as in the first fluorinated polymer of the present disclosure. From the viewpoint of reducing the dielectric loss tangent, it is preferably produced under the conditions taking into account the above methods 1 to 4.

[0367] The third composition for metal-clad laminates of the present disclosure comprises the third fluorinated polymer of the present disclosure and a solvent.

[0368] In the third metal-clad laminate composition disclosed herein, by making the fluorine-containing polymer have the above-mentioned structure, the compatibility with epoxy resin is excellent. In addition, by being used in the resin layer of the metal-clad laminate, the resin layer can have a low dielectric constant and a low dielectric loss tangent. The present disclosure provides the use of the above-mentioned metal-clad laminate composition in the metal-clad laminate (resin layer of the metal-clad laminate).

[0369] The third composition for metal-clad laminated sheets of the present disclosure contains a solvent. The solvent is the same as that in the first composition for metal-clad laminated sheets of the present disclosure.

[0370] The third composition for metal-clad laminates of the present disclosure may further include a curing accelerator. The curing accelerator is the same as that in the first composition for metal-clad laminates of the present disclosure. These substances may be used alone or in combination of two or more.

[0371] In the third composition for metal-clad laminate disclosed in the present invention, the above-mentioned fluorine-containing polymer is preferably 10 mass% or more, more preferably 25 mass% or more, and further preferably 40 mass% or more, relative to 100 mass% of the solid content. In addition, it can be less than 100 mass% or less than 80 mass%.

[0372] The third composition for metal-clad laminates of the present disclosure may not contain an epoxy resin.

[0373] The third curable composition of the present disclosure comprises the third fluorinated polymer of the present disclosure and an epoxy resin. The compatibility between the fluorinated polymer and the epoxy resin proposed in the resin layer of the conventional metal-clad laminate is not yet sufficient.

[0374] The third curable composition of the present disclosure contains the third fluorinated polymer of the present disclosure, and has excellent compatibility with epoxy resin, and therefore has a low dielectric constant and a low dielectric loss tangent, and also has excellent dispersibility, moisture resistance, heat resistance, flame retardancy, and adhesiveness.

[0375] In addition, by including the third fluorinated polymer of the present disclosure, a resin layer having a low dielectric constant and a low dielectric loss tangent can be formed, and thus the resin layer is particularly suitable for forming a resin layer of a metal-clad laminate.

[0376] The third curable composition of the present disclosure is preferably a curable composition for metal-clad laminates. The present disclosure provides use of the above curable composition in metal-clad laminates (resin layer of metal-clad laminates).

[0377] In the third curable composition of the present disclosure, the epoxy resin is the same as in the first curable composition of the present disclosure, and all the aspects described in the first curable composition can be adopted.

[0378] In the third curable composition of the present disclosure, the ratio (value obtained by multiplying the mass of the fluorinated polymer by the equivalent of the vinyl ester monomer unit) / (value obtained by multiplying the mass of the epoxy resin by the epoxy equivalent) is preferably 0.4 to 2.0. It is more preferably 0.5 to 1.5, further preferably 0.7 to 1.3, still more preferably 0.8 to 1.2, and particularly preferably 0.9 to 1.1. By making the above ratio within the above range, the fluorinated polymer and the epoxy resin can be cured efficiently.

[0379] In the third curable composition disclosed herein, from the aspects of dielectric constant, dielectric loss tangent, dispersibility, moisture resistance, heat resistance, flame retardancy, and adhesiveness, the epoxy resin preferably contains 1 part by mass or more, more preferably 50 parts by mass or more, and further preferably 80 parts by mass or more, relative to 100 parts by mass of the fluorinated polymer. In addition, the epoxy resin preferably contains 1000 parts by mass or less, more preferably 500 parts by mass or less, further preferably 300 parts by mass or less, and particularly preferably 200 parts by mass or less, relative to 100 parts by mass of the fluorinated polymer.

[0380] The third curable composition of the present disclosure may contain a flame retardant, an inorganic filler, a silane coupling agent, a release agent, a pigment, an emulsifier, and the like in addition to the epoxy resin.

[0381] The third curable composition of the present disclosure preferably further comprises a curing accelerator. The curing accelerator is the same as that in the first curable composition of the present disclosure. These substances may be used alone or in combination of two or more.

[0382] The third curable composition of the present disclosure may contain various additives according to the required properties. Examples of the additives include pigment dispersants, defoamers, leveling agents, UV absorbers, light stabilizers, thickeners, adhesion improvers, matting agents, and the like.

[0383] When the third curable composition of the present disclosure contains the above-mentioned various additives, in the third curable composition of the present disclosure, the total amount of the third fluorinated polymer of the present disclosure and the epoxy resin relative to 100 mass% of the solid content is preferably 5 mass% or more, more preferably 50 mass% or more, further preferably 70 mass% or more, and even more preferably 80 mass% or more.

[0384] The third curable composition of the present disclosure preferably contains an organic solvent. As an organic solvent, it is the same as in the first curable composition of the present disclosure. In the third curable composition of the present disclosure, the solid content concentration is preferably 10 to 80% by mass based on the total amount of the third fluorinated polymer and the epoxy resin of the present disclosure. When the solid content concentration is within this range, the viscosity of the curable composition is appropriate and can be applied to form a uniform coating film.

[0385] The method for preparing the third curable composition of the present disclosure is not particularly limited, and examples thereof include a method of mixing a solution or dispersion of a fluorine-containing polymer with a solution or dispersion of an epoxy resin.

[0386] The third curable composition disclosed herein can be used as a resin layer of a metal-clad laminate, and can also be used as a resin for powder coatings or a resin for optical applications.

[0387] The third metal-clad laminate of the present disclosure is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, wherein the resin layer is formed from the third curable composition of the present disclosure. The resin layer can be formed by curing the third curable composition of the present disclosure.

[0388] The third metal-clad laminate disclosed in the present invention is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, wherein the resin layer comprises a fluorine-containing polymer and an epoxy resin, the fluorine-containing polymer comprises polymer units based on a fluorine-containing vinyl monomer and polymer units based on a vinyl ester monomer, the total content of the polymer units based on the fluorine-containing vinyl monomer and the polymer units based on the vinyl ester monomer is 70 to 100 mol% relative to all polymer units, the fluorine-containing vinyl monomer comprises at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene and chlorotrifluoroethylene, and the fluorine-containing vinyl monomer comprises tetrafluoroethylene. When the above-mentioned fluorine-containing vinyl monomer includes hexafluoropropylene, the integral value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR is less than 2% relative to the integral value of CF as a whole. When the above-mentioned fluorine-containing vinyl monomer includes chlorotrifluoroethylene, the total integral value of CF2H at the terminal of -CF2H in 19F-NMR and the integral value of CFClH at the terminal of -CFClH are less than 2% relative to the total integral value of CF as a whole and the integral value of CFCl as a whole.

[0389] The third metal-clad laminate of the present disclosure comprises a metal foil and a resin layer. The resin layer has excellent insulating properties and functions as a base material of the metal-clad laminate.

[0390] The metal foil is the same as that in the first metal-clad laminate of the present disclosure.

[0391] In the resin layer, the epoxy resin preferably contains 1 part by mass or more, more preferably 10 parts by mass or more, further preferably 50 parts by mass or more, and particularly preferably 80 parts by mass or more, relative to 100 parts by mass of the third fluorinated polymer disclosed herein. In addition, the epoxy resin preferably contains 1000 parts by mass or less, more preferably 500 parts by mass or less, further preferably 300 parts by mass or less, and particularly preferably 200 parts by mass or less, relative to 100 parts by mass of the fluorinated polymer. If there is too much fluorinated polymer, the adhesiveness may be reduced; if there is too much epoxy resin, the insulation, moisture resistance, heat resistance, and flame retardancy may be reduced.

[0392] The resin layer is obtained from the third curable composition of the present disclosure. Since the fluorinated polymer and the epoxy resin are crosslinked, the above ratio is the ratio of the resin portion derived from the epoxy resin to 100 parts by mass of the resin portion derived from the fluorinated polymer.

[0393] The third metal-clad laminate of the present disclosure may further include other layers as long as it includes a metal foil and the resin layer. The metal foil and the resin layer may each be one type or two or more types.

[0394] The third metal-clad laminate of the present disclosure may further include a second resin layer provided on the above-mentioned resin layer (hereinafter referred to as "first resin layer"). That is, the third metal-clad laminate of the present disclosure may be formed by laminating the metal foil, the first resin layer and the second resin layer in this order. The first resin layer plays a role as a base material, and also plays a role as an adhesive layer for bonding the metal foil and the second resin layer.

[0395] In addition, in the third metal-clad laminate of the present disclosure, the first resin layer may be provided on a surface of the metal foil different from the surface on which the first resin layer is provided (the surface on the opposite side). That is, the third metal-clad laminate of the present disclosure may be laminated in the order of the first resin layer, the metal foil, and the first resin layer, or in the order of the first resin layer, the metal foil, the first resin layer, and the second resin layer.

[0396] The second resin layer may be made of a resin used in conventional printed circuit boards. The second resin layer is preferably made of at least one resin selected from the group consisting of polyethylene terephthalate and polyimide, and is more preferably made of polyimide from the viewpoint of heat resistance.

[0397] As the first resin layer, a film having a thickness of 1 to 150 μm may be used. When the metal foil and the second adhesive layer are bonded to each other via the first resin layer, the thickness of the first resin layer after drying may be 1 to 100 μm.

[0398] As the second resin layer, a resin film having a thickness of 1 to 150 μm can be used.

[0399] The third metal-clad laminate of the present disclosure can be produced by the same method as the first metal-clad laminate of the present disclosure, except that the third fluorine-containing polymer of the present disclosure is used as the fluorine-containing polymer.

[0400] The present disclosure also provides a printed circuit board (the third printed circuit board of the present disclosure), characterized in that it has a pattern circuit formed by etching the metal foil of the third metal-clad laminate of the present disclosure. The third printed circuit board of the present disclosure can be a flexible substrate or a rigid substrate, preferably a flexible substrate.

[0401] The third printed circuit board of the present disclosure may include a coverlay film on the metal-clad laminate, and the coverlay film may be bonded to the metal-clad laminate via the resin layer.

[0402] The etching method is not limited, and a conventionally known method can be used. In addition, the pattern circuit is not limited, and any pattern circuit printed substrate can be used.

[0403] The third printed circuit board of the present disclosure is not limited in its use. For example, since the third printed circuit board of the present disclosure has a resin layer with a low dielectric constant and a low dielectric loss tangent, it can also be used in printed circuit boards used in applications with high bandwidths such as 4G (37.5Mbps) and 5G (several G to 20Gbps).

[0404] The epoxy resin disclosed in the present invention is characterized in that it contains a polymerized unit based on tetrafluoroethylene and / or a polymerized unit based on hexafluoropropylene, and a polymerized unit based on allyl glycidyl ether, and the total content of the polymerized unit based on tetrafluoroethylene, the polymerized unit based on hexafluoropropylene, and the polymerized unit based on allyl glycidyl ether is 98 to 100 mol% relative to the total polymerized units. In the case of a polymerized unit based on tetrafluoroethylene, the integral value of CF2H at the terminal of -CF2H in 19F-NMR is 4% or less relative to the integral value of the entire CF2, and in the case of a polymerized unit based on hexafluoropropylene, the integral value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR is 4% or less relative to the integral value of the entire CF. The epoxy resin disclosed in the present invention can increase the gel fraction after immersion in acetone by having the above-mentioned structure.

[0405] The epoxy resin disclosed herein contains polymerized units based on tetrafluoroethylene (TFE) (hereinafter referred to as "TFE units") and / or polymerized units based on hexafluoropropylene (HFP) (hereinafter referred to as "HFP units"). The epoxy resin preferably contains TFE units because of excellent copolymerizability.

[0406] The total content of the TFE unit and the HFP unit is preferably 10 mol% or more, more preferably 20 mol% or more, further preferably 30 mol% or more, and particularly preferably 40 mol% or more, relative to the total polymerized units of the epoxy resin disclosed herein. In addition, it is preferably 80 mol% or less, more preferably 70 mol% or less, further preferably 60 mol% or less, and particularly preferably 50 mol% or less.

[0407] The epoxy resin of the present disclosure includes polymerized units based on allyl glycidyl ether (AGE) (hereinafter referred to as “AGE units”).

[0408] The AGE unit is preferably 10 mol% or more, more preferably 20 mol% or more, further preferably 30 mol% or more, still more preferably 40 mol% or more, and particularly preferably 50 mol% or more, based on all polymerized units of the epoxy resin disclosed herein. It is also preferably 80 mol% or less, more preferably 70 mol% or less, and further preferably 60 mol% or less.

[0409] In the epoxy resin disclosed herein, the total content of TFE units, HFP units, and AGE units is 98 to 100 mol% relative to all polymerized units of the epoxy resin. From the perspective of gel fraction after immersion in acetone, it is preferably 99 to 100 mol%, and more preferably 100 mol%. That is, the epoxy resin disclosed herein is preferably substantially composed of only TFE units, HFP units, and AGE units.

[0410] When the epoxy resin disclosed herein contains a TFE unit, the integral value of CF2H at the -CF2H terminal in 19F-NMR is preferably 4% or less relative to the integral value of CF2 as a whole. In this way, by reducing the proportion of -CF2H terminals, the gel fraction after acetone immersion can be increased. In order to further increase the gel fraction after acetone immersion, the integral value of CF2H at the -CF2H terminal in 19F-NMR is preferably 3% or less relative to the integral value of CF2 as a whole.

[0411] When the epoxy resin disclosed herein contains HFP units, the integral value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR is preferably 4% or less relative to the integral value of CF as a whole. In this way, by reducing the proportion of -CF2CFHCF3 terminals, the gel fraction after acetone immersion can be increased. In order to further increase the gel fraction after acetone immersion, the integral value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR is preferably 3% or less relative to the integral value of CF as a whole.

[0412] For example, the proportions of -CF2H terminals and -CF2CFHCF3 terminals can be reduced by methods 1 to 4 described in connection with the third fluorinated polymer of the present disclosure.

[0413] The number average molecular weight of the epoxy resin disclosed in the present invention is preferably 500 to 10000. When the number average molecular weight is in such a range, it can react effectively with the fluorine-containing polymer containing active ester, and the resin layer of the metal-clad laminate can be firmly bonded to the metal foil. As a number average molecular weight, it is more preferably 1000 or more. In addition, it is more preferably 8000 or less, further preferably 6000 or less, and particularly preferably 4000 or less.

[0414] The number average molecular weight of the epoxy resin can be measured by gel permeation chromatography (GPC).

[0415] The epoxy resin of the present disclosure is preferably a liquid at 25° C. This allows for good compatibility with other polymers (resins).

[0416] Such properties can be achieved, for example, by lowering the molecular weight and Tg of the epoxy resin.

[0417] The fluorine content of the epoxy resin disclosed herein is preferably 20% by mass or more, and more preferably 25% by mass or more. The fluorine content of the epoxy resin can be determined by elemental analysis using an automatic sample combustion device.

[0418] The epoxy equivalent of the epoxy resin disclosed in the present invention is preferably 50 to 5000 g / eg, more preferably 50 to 1000 g / eg, and even more preferably 50 to 500 g / eg.

[0419] The epoxy equivalent is determined in accordance with JIS7236.

[0420] The glass transition temperature of the epoxy resin disclosed herein is preferably 20° C. or lower, more preferably 10° C. or lower, and further preferably 0° C. or lower. It is preferably -100° C. or higher, more preferably -60° C. or higher, and further preferably -40° C. or higher.

[0421] The epoxy resin of the present disclosure can be produced by the same method as the first fluorinated polymer of the present disclosure.

[0422] The fourth curable composition of the present disclosure contains the epoxy resin of the present disclosure and the third fluorinated polymer of the present disclosure.

[0423] The fourth curable composition of the present disclosure contains the third fluorinated polymer of the present disclosure, and thus has the same advantages as the third curable composition of the present disclosure. In addition, by containing the epoxy resin of the present disclosure, properties such as adhesiveness can be further improved.

[0424] The fourth curable composition of the present disclosure is preferably a curable composition for metal-clad laminates. The present disclosure provides use of the above curable composition in metal-clad laminates (resin layer of metal-clad laminates).

[0425] In addition, the epoxy resin of the present disclosure can be combined with the first fluorinated polymer of the present disclosure and the second fluorinated polymer of the present disclosure to form a curable composition.

[0426] In the fourth curable composition of the present disclosure, the ratio (value obtained by multiplying the mass of the fluorinated polymer by the equivalent of the vinyl ester monomer unit) / (value obtained by multiplying the mass of the epoxy resin by the epoxy equivalent) is preferably 0.4 to 2.0. It is more preferably 0.5 to 1.5, further preferably 0.7 to 1.3, still more preferably 0.8 to 1.2, and particularly preferably 0.9 to 1.1. By making the above ratio within the above range, the fluorinated polymer and the epoxy resin can be cured efficiently.

[0427] In the fourth curable composition of the present disclosure, from the aspects of dielectric constant, dielectric loss tangent, dispersibility, moisture resistance, heat resistance, flame retardancy, and adhesiveness, the epoxy resin preferably contains 1 mass part or more, more preferably 50 mass parts or more, and further preferably 80 mass parts or more, relative to 100 mass parts of the fluorinated polymer. In addition, the epoxy resin preferably contains 1000 mass parts or less, more preferably 500 mass parts or less, further preferably 300 mass parts or less, and particularly preferably 200 mass parts or less, relative to 100 mass parts of the fluorinated polymer.

[0428] The fourth curable composition of the present disclosure may contain a flame retardant, an inorganic filler, a silane coupling agent, a release agent, a pigment, an emulsifier, and the like in addition to the fluorine-containing polymer and the epoxy resin.

[0429] The fourth curable composition of the present disclosure preferably further comprises a curing accelerator. The curing accelerator is the same as that in the first curable composition of the present disclosure. These substances may be used alone or in combination of two or more.

[0430] The fourth curable composition of the present disclosure may contain various additives according to the required properties. Examples of the additives include pigment dispersants, defoamers, leveling agents, UV absorbers, light stabilizers, thickeners, adhesion improvers, matting agents, and the like.

[0431] When the fourth curable composition of the present disclosure contains the above-mentioned various additives, in the third curable composition of the present disclosure, the total amount of the third fluorinated polymer of the present disclosure and the epoxy resin of the present disclosure relative to 100 mass% of the solid content is preferably 5 mass% or more, more preferably 50 mass% or more, further preferably 70 mass% or more, and even more preferably 80 mass% or more.

[0432] The fourth curable composition of the present disclosure preferably contains an organic solvent. As the organic solvent, it is the same as in the first curable composition of the present disclosure. In the fourth curable composition of the present disclosure, the solid content concentration is preferably 10 to 80% by mass based on the total amount of the third fluorinated polymer of the present disclosure and the epoxy resin of the present disclosure. When the solid content concentration is within this range, the viscosity of the curable composition is appropriate and can be applied to form a uniform coating film.

[0433] The method for preparing the fourth curable composition of the present disclosure is not particularly limited, and examples thereof include a method of mixing a solution or dispersion of a fluorine-containing polymer with a solution or dispersion of an epoxy resin.

[0434] The fourth curable composition of the present disclosure can be used as a resin layer of a metal-clad laminate, and can also be used as a resin for powder coatings or a resin for optical applications.

[0435] The fourth metal-clad laminate of the present disclosure is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, wherein the resin layer is formed from the fourth curable composition of the present disclosure. The resin layer can be formed by curing the fourth curable composition of the present disclosure.

[0436] The fourth metal-clad laminate disclosed in the present invention is a metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, wherein the resin layer comprises a fluorine-containing polymer and an epoxy resin, wherein the fluorine-containing polymer comprises a polymerized unit based on a fluorine-containing vinyl monomer and a polymerized unit based on a vinyl ester monomer, wherein the total content of the polymerized unit based on the fluorine-containing vinyl monomer and the polymerized unit based on the vinyl ester monomer is 70 to 100 mol % relative to all the polymerized units, wherein the fluorine-containing vinyl monomer comprises at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene and chlorotrifluoroethylene, wherein when the fluorine-containing vinyl monomer comprises tetrafluoroethylene, the integral value of CF2H at the terminal of -CF2H in 19F-NMR relative to the integral value of the entire CF2 is 2% or less, and when the fluorine-containing vinyl monomer comprises hexafluoropropylene, the integral value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR relative to the integral value of the entire CF is The integral value is 2% or less. When the fluorine-containing vinyl monomer includes chlorotrifluoroethylene, the integral value of CF2H at the end of -CF2H and the integral value of CFClH at the end of -CFClH in 19F-NMR is 2% or less relative to the total integral value of CF2 as a whole and the integral value of CFCl as a whole. The epoxy resin is composed only of polymerization units based on tetrafluoroethylene and / or polymerization units based on hexafluoropropylene and polymerization units based on allyl glycidyl ether, has a number average molecular weight of 500 to 10000, and is liquid at 25°C. When the polymerization units are based on tetrafluoroethylene, the integral value of CF2H at the end of -CF2H in 19F-NMR is 4% or less relative to the integral value of CF2 as a whole. When the polymerization units are based on hexafluoropropylene, the integral value of CFH at the end of -CF2CFHCF3 in 19F-NMR is 4% or less relative to the integral value of CF as a whole.

[0437] The fourth metal-clad laminate of the present disclosure comprises a metal foil and a resin layer. The resin layer has excellent insulating properties and functions as a base material of the metal-clad laminate.

[0438] The metal foil is the same as that in the first metal-clad laminate of the present disclosure.

[0439] In the resin layer, the epoxy resin preferably contains 1 part by mass or more, more preferably 10 parts by mass or more, further preferably 50 parts by mass or more, and particularly preferably 80 parts by mass or more, relative to 100 parts by mass of the fluoropolymer. In addition, the epoxy resin preferably contains 1000 parts by mass or less, more preferably 500 parts by mass or less, further preferably 300 parts by mass or less, and particularly preferably 200 parts by mass or less, relative to 100 parts by mass of the fluoropolymer. If the fluoropolymer is too much, the adhesiveness may be reduced; if the epoxy resin is too much, the insulation, moisture resistance, heat resistance, and flame retardancy may be reduced.

[0440] The resin layer is obtained from the fourth curable composition of the present disclosure. Since the fluorinated polymer and the epoxy resin are crosslinked, the above ratio is the ratio of the resin portion derived from the epoxy resin to 100 parts by mass of the resin portion derived from the fluorinated polymer.

[0441] The third metal-clad laminate of the present disclosure may further include other layers as long as it includes a metal foil and the resin layer. The metal foil and the resin layer may each be one type or two or more types.

[0442] The fourth metal-clad laminate of the present disclosure may further include a second resin layer provided on the above-mentioned resin layer (hereinafter referred to as "first resin layer"). That is, the fourth metal-clad laminate of the present disclosure may be formed by laminating the metal foil, the first resin layer and the second resin layer in this order. The first resin layer plays a role as a base material, and also plays a role as an adhesive layer for bonding the metal foil and the second resin layer.

[0443] In addition, in the fourth metal-clad laminate of the present disclosure, the first resin layer may be provided on a surface of the metal foil different from the surface on which the first resin layer is provided (the surface on the opposite side). That is, the fourth metal-clad laminate of the present disclosure may be laminated in the order of the first resin layer, the metal foil, and the first resin layer, or in the order of the first resin layer, the metal foil, the first resin layer, and the second resin layer.

[0444] The second resin layer may be made of a resin used in conventional printed circuit boards. The second resin layer is preferably made of at least one resin selected from the group consisting of polyethylene terephthalate and polyimide, and is more preferably made of polyimide from the viewpoint of heat resistance.

[0445] As the first resin layer, a film having a thickness of 1 to 150 μm may be used. When the metal foil and the second adhesive layer are bonded to each other via the first resin layer, the thickness of the first resin layer after drying may be 1 to 100 μm.

[0446] As the second resin layer, a resin film having a thickness of 1 to 150 μm can be used.

[0447] The fourth metal-clad laminate of the present disclosure can be produced by the same method as the first metal-clad laminate of the present disclosure, except that the third fluorine-containing polymer of the present disclosure is used as the fluorine-containing polymer and the epoxy resin of the present disclosure is used as the epoxy resin.

[0448] The present disclosure also provides a printed circuit board (the fourth printed circuit board of the present disclosure), characterized in that it has a pattern circuit formed by etching the metal foil of the fourth metal-clad laminate of the present disclosure. The fourth printed circuit board of the present disclosure can be a flexible substrate or a rigid substrate, preferably a flexible substrate.

[0449] The fourth printed circuit board of the present disclosure may include a coverlay film on the metal-clad laminate, and the coverlay film may be bonded to the metal-clad laminate via the resin layer.

[0450] The etching method is not limited, and a conventionally known method can be used. In addition, the pattern circuit is not limited, and any pattern circuit printed substrate can be used.

[0451] The use of the fourth printed circuit board disclosed in the present invention is not limited. For example, since the fourth printed circuit board disclosed in the present invention has a resin layer with a low dielectric constant and a low dielectric loss tangent, it can also be used in printed circuit boards used for applications with high bandwidths such as 4G (37.5Mbps) and 5G (several G to 20Gbps).

[0452] Example

[0453] Next, the present invention will be described with reference to Examples, but the present invention is not limited to the Examples.

[0454] The present invention is described in more detail below by way of examples.

[0455] The physical properties described in this specification were measured by the following measurement methods.

[0456] (1) NMR analysis:

[0457] Measuring device: NMR measuring device: manufactured by VARIAN

[0458] 1H-NMR measurement conditions: 400 MHz (tetramethylsilane = 0 ppm)

[0459] (2) Elemental analysis (determination of fluorine content (mass %))

[0460] Measuring device: Automatic sample combustion device (AQF-100 manufactured by Mitsubishi Chemical Corporation) with built-in ion chromatograph (ICS-1500 Ion Chromatography System manufactured by DIONEX Corporation)

[0461] Sample 3mg

[0462] (3) Molecular weight

[0463] Measuring device: Shodex GPC-104 manufactured by Showa Denko K.K.

[0464] Measurement conditions: Tetrahydrofuran was used as the eluent, and polystyrene with a known molecular weight was used as a molecular weight standard sample.

[0465] (4) Glass transition temperature

[0466] The glass transition temperature and the crystalline melting point were determined by a midpoint method based on heat absorption in the second run using a DSC measuring apparatus manufactured by METLER TOLEDO in accordance with ASTM E1356-98.

[0467] Measurement conditions

[0468] Heating rate: 20℃ / min

[0469] Sample volume: 10 mg

[0470] Thermal cycle: -50℃~150℃, heating, cooling, heating

[0471] (5) Infrared spectroscopy

[0472] Measuring device: Perkin-Elmer FTIR spectrometer 1760X (manufactured by Perkin Elmer)

[0473] In the measurement, a powder or film-like sample is scanned 40 times to obtain an infrared spectrum.

[0474] Example 1

[0475] Into a 3000ml stainless steel autoclave, 1050g of acetone and 130g of vinyl benzoate (VBz) were added, and the atmosphere was replaced with nitrogen under reduced pressure, and 130g of tetrafluoroethylene (TFE) was added. The mixture was heated to a suitable temperature under stirring, and 8g of a peroxide polymerization initiator was added to initiate polymerization. The reaction was stopped when the internal pressure of the reactor dropped from 1.0MPaG to 0.4MPaG, and a solution containing a polymer was obtained. The obtained solution was concentrated and dried to obtain a fluorine-containing polymer.

[0476] According to NMR analysis, the obtained fluorine-containing polymer has a composition of 50 mol% of tetrafluoroethylene and 50 mol% of vinyl benzoate. According to molecular weight analysis, the number average molecular weight (Mn) is 11000. The glass transition temperature (Tg) is 66°C. According to the results of elemental analysis, the fluorine content is 30.3% by mass.

[0477] The vinyl ester unit equivalent calculated from the composition was 248 g / eq.

[0478] Comparative Example 1

[0479] Into a 6000ml stainless steel autoclave, 2500g of butyl acetate, 584g of neononanoic acid vinyl ester (NNVE), 77g of vinyl benzoate (VBz), 527g of 4-hydroxybutyl vinyl ether (HBVE), and 7g of crotonic acid (CA) were added, and the pressure was reduced and replaced with nitrogen. 658g of tetrafluoroethylene (TFE) was added. The temperature was raised to a suitable temperature under stirring, and 30g of a peroxide polymerization initiator was added to initiate polymerization. The reaction was stopped when the internal pressure of the reactor dropped from 1.0MPaG to 0.4MPaG, and a solution containing a polymer was obtained. The obtained solution was concentrated and dried to obtain a fluorine-containing polymer.

[0480] According to NMR analysis, the obtained fluorine-containing polymer is composed of 45.0 mol% of tetrafluoroethylene, 33.3 mol% of vinyl neononanoate, 5.5 mol% of vinyl benzoate, 15.3 mol% of 4-hydroxybutyl vinyl ether, and 0.9 mol% of crotonic acid. According to molecular weight analysis, the number average molecular weight (Mn) is 16000. The glass transition temperature (Tg) is 30°C. According to the results of elemental analysis, the fluorine content is 27.0 mass%.

[0481] In addition, the infrared spectrum of the dried and solidified product of the fluorinated polymer obtained in Example 1 after immersion in acetone was measured. As a result, the characteristic absorption (1728 cm -1 、1108cm -1 、710cm -1 ) and the characteristic absorption of the epoxy resin used (2947cm -1 、1602cm -1 、1491cm -1 、752cm -1 ) both, it can be seen that the fluorine-containing polymer reacts with the epoxy resin and functions as an active ester.

[0482] Example 2

[0483] In a 3000 ml stainless steel autoclave, a nitrogen replacement operation was performed under reduced pressure, and 900 g of acetone and 130 g of tetrafluoroethylene (TFE) were added. The temperature was raised to 70.0°C under stirring, and 8 g of a peroxide polymerization initiator was added. At the same time, a mixed solution of 142 g of vinyl benzoate (VBz) and 71 g of acetone was added at 3 ml per minute to initiate polymerization. The reaction was stopped when the internal pressure of the reactor dropped from 1.0 MPaG to 0.4 MPaG, and a solution containing a polymer was obtained. The obtained solution was concentrated and dried to obtain a fluorine-containing polymer.

[0484] According to NMR analysis, the obtained fluorine-containing polymer is composed of 54 mol% of TFE and 46 mol% of vinyl benzoate. According to molecular weight analysis, the number average molecular weight (Mn) is 9000. The glass transition temperature (Tg) is 54°C. According to the results of elemental analysis, the fluorine content is 33.3% by mass. The vinyl ester unit equivalent calculated based on the composition is 263 g / eq.

[0485] Example 3

[0486] In Example 1, the reaction was carried out in the same manner as in Example 1, except that 87 g of vinyl benzoate was used and 60 g of isobornyl acrylate was added, thereby obtaining a fluorinated polymer.

[0487] According to NMR analysis, the obtained fluorine-containing polymer is composed of 47 mol% of tetrafluoroethylene, 34 mol% of vinyl benzoate (VBz), and 19 mol% of isobornyl acrylate (IBAC). According to molecular weight analysis, the number average molecular weight (Mn) is 8000. The glass transition temperature (Tg) is 61°C. According to the results of elemental analysis, the fluorine content is 26.3% by mass. The vinyl ester unit equivalent calculated based on the composition is 402g / eq.

[0488] The compatibility evaluation was carried out as follows.

[0489] The fluorinated polymers obtained in Examples and Comparative Examples were dissolved in methyl ethyl ketone to adjust the solid content to 50% by mass. Also, a solution of an epoxy resin (epoxy equivalent: 259 g / eq) was prepared similarly to adjust the solid content to 80% by mass.

[0490] Next, the two solutions were mixed by adjusting the blending amount so that the vinyl ester unit equivalent and the epoxy equivalent were the same. The appearance of the mixed solution was visually observed to evaluate the compatibility. The compatibility evaluation was determined as follows.

[0491] The state of the mixed solution

[0492] Transparent: 0 (good compatibility)

[0493] Opaque: × (poor compatibility)

[0494] The results are shown in Table 1.

[0495] The reactivity evaluation with the epoxy resin was carried out as follows.

[0496] To the mixed liquid, 0.5% by mass of 4-dimethylaminopyridine was added based on the solid content of the solution, and the mixture was mixed well to prepare a curing composition.

[0497] 10 g of the curable composition was taken and dried in a 50° C. air dryer for 3 hours, and then reacted in a 175° C. air dryer for 12 hours. After the reaction, the cured product was cooled.

[0498] Next, the gel fraction was measured as an index of the reaction degree of the cured product.

[0499] The solidified product was collected and covered with a pre-weighed 400-mesh wire mesh. 25 ml of acetone and the solidified product covered with the wire mesh were added to a 50 ml sample tube, and the solidified product was immersed in acetone for 12 hours. The wire mesh was then removed, dried, and the weight after drying was measured to calculate the weight of the dried solidified product after immersion in acetone.

[0500] The gel fraction was calculated as weight of the dried solidified product after immersion in acetone / weight of the solidified product before immersion in acetone×100. The results are shown in Table 1.

[0501] [Table 1]

[0502]

[0503] In addition, the compatibility evaluation and reactivity evaluation of the resins of Examples 2 and 3 with the epoxy resin were as described above.

[0504] In addition, the arrangement of monomers in the polymer (chain segments) was determined by NMR analysis. In the case of tetrafluoroethylene (T) and vinyl ester (V), in the case of vinyl benzoate, there is a peak at around 6.1ppm in the chain segments arranged in TVT. Similarly, the TVVT chain segment has a peak at around 5.9ppm, and the TVVVT chain segment has a peak at around 5.6ppm. Based on this, the ratio of each chain segment is calculated from the peak area of ​​each NMR. The calculated results are shown in Table 2.

[0505] [Table 2]

[0506]

[0507]

[0508] It is understood from Examples 1 and 2 that when the segment TVT of vinyl benzoate in the polymer increases, the reactivity with the epoxy resin is improved and the gel fraction increases.

[0509] It is understood from Examples 1 and 2 that when the molecular weight of the polymer is reduced, the reactivity with the epoxy resin is improved and the gel fraction is increased.

[0510] It is clear from Examples 1 and 3 that when isobornyl acrylate is used as the third component, the reactivity with the epoxy resin is good and the gel fraction is increased.

[0511] Synthesis example 1

[0512] 1000 g of acetone as a solvent was placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the bath temperature was raised to 70° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the bath reached 0.79 MPa.

[0513] Then, 4.2 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and the supply of vinyl benzoate (VBz) was started at the same time. Vinyl benzoate was added at 1.5 ml / min to a total of 150 g. Tetrafluoroethylene was also continuously supplied during the reaction to keep the pressure in the tank at 0.775 to 0.7795 MPa.

[0514] One hour after the reaction started, 4.2 g of Perbutyl PV was further added. After the supply of vinyl benzoate was stopped, the supply of tetrafluoroethylene was also stopped. The bath temperature was further set to 75° C., and the aging reaction was continued for another hour.

[0515] Thereafter, the temperature and pressure in the tank were returned to normal to terminate the polymerization, thereby obtaining an acetone solution of a vinyl benzoate / tetrafluoroethylene copolymer (solid content concentration: 17% by mass).

[0516] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0517] According to NMR analysis, the obtained fluorine-containing polymer has a composition of 50 mol% of tetrafluoroethylene and 50 mol% of vinyl benzoate. According to molecular weight analysis, the number average molecular weight (Mn) is 12000. The glass transition temperature (Tg) is 66°C. According to the results of elemental analysis, the fluorine content is 30.3% by mass.

[0518] The vinyl ester unit equivalent calculated from the composition was 248 g / eq.

[0519] Synthesis example 2

[0520] 900 g of acetone as a solvent was placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the bath temperature was raised to 70° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the bath reached 0.79 MPa.

[0521] Then, 4.2 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and at the same time, a mixed solution of 140 g of vinyl benzoate and 70 g of acetone was started to be supplied. A total of 200 g of the mixed solution of vinyl benzoate and acetone was added at 1.5 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction so that the pressure in the tank was 0.775 to 0.7795 MPa.

[0522] One hour after the start of the reaction, 4.2 g of Perbutyl PV was further added. After the supply of the mixed solution of vinyl benzoate and acetone was stopped, the supply of tetrafluoroethylene was also stopped. The bath temperature was further set to 75° C., and the aging reaction was continued for 2 hours.

[0523] Thereafter, the temperature and pressure in the tank were returned to normal to terminate the polymerization, thereby obtaining an acetone solution of a vinyl benzoate / tetrafluoroethylene copolymer (solid content concentration: 21% by mass).

[0524] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0525] According to NMR analysis, the obtained fluorine-containing polymer has a composition of 60 mol% of tetrafluoroethylene and 40 mol% of vinyl benzoate. According to molecular weight analysis, the number average molecular weight (Mn) is 9600. The glass transition temperature (Tg) is 55° C. According to the results of elemental analysis, the fluorine content is 33.3% by mass.

[0526] The vinyl ester unit equivalent calculated from the composition was 263 g / eq.

[0527] Synthesis example 3

[0528] 800 g of acetone and 20 g of vinyl benzoate as solvents were placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the tank temperature was raised to 70° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the tank reached 0.79 MPa.

[0529] Then, 4.2 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and the supply of vinyl benzoate was started at the same time. A total of 100 g of vinyl benzoate was added at 2.5 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction to keep the pressure in the tank at 0.775 to 0.7795 MPa.

[0530] After the supply of vinyl benzoate was stopped, the supply of tetrafluoroethylene was also stopped, and the temperature and pressure in the tank were returned to normal to stop the polymerization, thereby obtaining an acetone solution of a vinyl benzoate / tetrafluoroethylene copolymer (solid content concentration: 14% by mass).

[0531] After the reaction is completed, the polymer solution is reprecipitated in a large amount of methanol solution, the polymer is purified, and dried to obtain a fluorine-containing polymer.

[0532] According to NMR analysis, the obtained fluorine-containing polymer had a composition of 41 mol% of tetrafluoroethylene and 59 mol% of vinyl benzoate. According to molecular weight analysis, the number average molecular weight (Mn) was 10,000. The glass transition temperature (Tg) was 62° C. According to the results of elemental analysis, the fluorine content was 23.5% by mass.

[0533] The vinyl ester unit equivalent weight calculated from the composition was 214 g / eq.

[0534] Synthesis example 4

[0535] 800 g of acetone and 20 g of vinyl pivalate (PV) as solvents were placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the tank temperature was raised to 60° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the tank reached 0.79 MPa.

[0536] Then, 2.1 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and the supply of vinyl pivalate was started at the same time. A total of 160 g of vinyl pivalate was added at 2.0 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction to keep the pressure in the tank at 0.775 to 0.7795 MPa.

[0537] After stopping the supply of vinyl pivalate, the supply of tetrafluoroethylene was also stopped, and the aging reaction was continued at 60°C for 1 hour, after which the tank was returned to normal temperature and pressure to stop the polymerization, thereby obtaining an acetone solution of vinyl pivalate / tetrafluoroethylene copolymer (solid content concentration 14% by mass).

[0538] After the reaction is completed, the polymer solution is reprecipitated in a large amount of methanol solution, the polymer is purified, and dried to obtain a fluorine-containing polymer.

[0539] According to NMR analysis, the obtained fluorine-containing polymer has a composition of 55 mol% of tetrafluoroethylene and 45 mol% of vinyl pivalate. According to molecular weight analysis, the number average molecular weight (Mn) is 14000. The glass transition temperature (Tg) is 45°C. According to the results of elemental analysis, the fluorine content is 37.1% by mass.

[0540] The vinyl ester unit equivalent calculated from the composition was 250 g / eq.

[0541] Synthesis example 5

[0542] 800 g of acetone as a solvent was placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the bath temperature was raised to 70° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the bath reached 0.79 MPa.

[0543] Then, 4.2 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and the supply of 4-tert-butyl benzoic acid vinyl ester (tert-BuVBz) was started at the same time. A total of 160 g of 4-tert-butyl benzoic acid vinyl ester was added at 2.0 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction to keep the pressure in the tank at 0.775 to 0.7795 MPa.

[0544] After the supply of 4-tert-butylvinylbenzoate was stopped, the supply of tetrafluoroethylene was also stopped, and the bath temperature was further lowered to 75° C., and the aging reaction was continued for 1 hour.

[0545] Thereafter, the temperature and pressure in the tank were returned to normal to terminate the polymerization, thereby obtaining an acetone solution of 4-tert-butylbenzoic acid vinyl ester / tetrafluoroethylene copolymer (solid content concentration: 27% by mass).

[0546] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0547] According to NMR analysis, the obtained fluorine-containing polymer has a composition of 45 mol% of tetrafluoroethylene and 55 mol% of 4-tert-butyl benzoic acid vinyl ester. According to molecular weight analysis, the number average molecular weight (Mn) is 9000. The glass transition temperature (Tg) is 85° C. According to the results of elemental analysis, the fluorine content is 34.5% by mass.

[0548] The vinyl ester unit equivalent calculated from the composition was 374 g / eq.

[0549] Synthesis example 6

[0550] 800 g of acetone and 40 g of 4-tert-butylvinylbenzoate as solvents were placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the tank temperature was raised to 65° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the tank reached 0.79 MPa.

[0551] Then, 2.1 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and the supply of 4-tert-butyl benzoic acid vinyl ester was started at the same time. A total of 120 g of 4-tert-butyl benzoic acid vinyl ester was added at 2.0 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction to keep the pressure in the tank at 0.775 to 0.7795 MPa.

[0552] After the supply of 4-tert-butylvinylbenzoate was stopped, the supply of tetrafluoroethylene was also stopped, and the aging reaction was continued for 0.5 hours while the bath temperature was kept at 65°C.

[0553] Thereafter, the temperature and pressure in the tank were returned to normal to terminate the polymerization, thereby obtaining an acetone solution of 4-tert-butylbenzoic acid vinyl ester / tetrafluoroethylene copolymer (solid content concentration: 22% by mass).

[0554] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0555] According to NMR analysis, the obtained fluorine-containing polymer has a composition of 52 mol% of tetrafluoroethylene and 48 mol% of 4-tert-butyl benzoic acid vinyl ester. According to molecular weight analysis, the number average molecular weight (Mn) is 12000. The glass transition temperature (Tg) is 107°C. According to the results of elemental analysis, the fluorine content is 26.1% by mass.

[0556] The vinyl ester unit equivalent calculated from the composition was 311 g / eq.

[0557] Synthesis Example 7

[0558] A 3 L stainless steel autoclave was charged with 800 g of acetone and 20 g of vinyl acetate as solvents, the autoclave was purged with nitrogen, and the tank temperature was raised to 70° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the tank reached 0.79 MPa.

[0559] Next, 2.1 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and the supply of vinyl acetate was started at the same time. A total of 110 g of vinyl acetate was added at 1.0 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction so that the pressure in the tank was 0.775 to 0.7795 MPa.

[0560] After the supply of vinyl acetate was stopped, the supply of tetrafluoroethylene was also stopped, and the aging reaction was further continued for 0.5 hours.

[0561] Thereafter, the inside of the tank was returned to normal temperature and pressure to terminate the polymerization, thereby obtaining an acetone solution of a vinyl acetate / tetrafluoroethylene copolymer (solid content concentration: 17% by mass).

[0562] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0563] According to NMR analysis, the obtained fluorine-containing polymer had a composition of 48 mol% of tetrafluoroethylene and 52 mol% of vinyl acetate. According to molecular weight analysis, the number average molecular weight (Mn) was 10,000. The glass transition temperature (Tg) was 35° C. According to the results of elemental analysis, the fluorine content was 39.3% by mass.

[0564] The vinyl ester unit equivalent calculated from the composition was 178 g / eq.

[0565] Synthesis example 8

[0566] 800 g of acetone and 20 g of vinyl benzoate as solvents were placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the bath temperature was raised to 70° C. 600 g of hexafluoropropylene was placed therein with stirring.

[0567] Next, 2.1 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and simultaneously the supply of vinyl benzoate was started. A total of 60 g of vinyl benzoate was added at 1.5 ml / min.

[0568] After the supply of vinyl benzoate was stopped, the reaction was continued for 4 hours at a temperature of 70°C in the tank.

[0569] The inside of the tank was returned to normal temperature and pressure to terminate the polymerization, thereby obtaining an acetone solution of a vinyl benzoate / hexafluoropropylene copolymer (solid content concentration: 14% by mass).

[0570] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0571] According to NMR analysis, the obtained fluorine-containing polymer had a composition of 37 mol% hexafluoropropylene and 63 mol% vinyl benzoate. According to molecular weight analysis, the number average molecular weight (Mn) was 7500. The glass transition temperature (Tg) was 45° C. According to the results of elemental analysis, the fluorine content was 28.1% by mass.

[0572] The vinyl ester unit equivalent calculated from the composition was 235 g / eq.

[0573] Synthesis example 9

[0574] 800 g of acetone and 20 g of vinyl pivalate as solvents were placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the bath temperature was raised to 70° C. 600 g of hexafluoropropylene was placed therein with stirring.

[0575] Next, 4.2 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and simultaneously the supply of vinyl pivalate was started. A total of 110 g of vinyl pivalate was added at 1.5 ml / min.

[0576] After the supply of vinyl pivalate was stopped, the inside of the tank was returned to normal temperature and pressure to stop the polymerization, thereby obtaining an acetone solution of vinyl pivalate / hexafluoropropylene copolymer (solid content concentration: 23% by mass).

[0577] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0578] According to NMR analysis, the obtained fluorine-containing polymer had a composition of 42 mol% hexafluoropropylene and 58 mol% vinyl pivalate. According to molecular weight analysis, the number average molecular weight (Mn) was 9000. The glass transition temperature (Tg) was 50° C. According to the results of elemental analysis, the fluorine content was 34.5% by mass.

[0579] The vinyl ester unit equivalent calculated from the composition was 234 g / eq.

[0580] Synthesis example 10

[0581] 800 g of acetone and 20 g of 4-tert-butylethylene benzoate were placed in a 3 L stainless steel autoclave as a solvent, the autoclave was purged with nitrogen, and the bath temperature was raised to 70° C. 600 g of hexafluoropropylene was placed therein with stirring.

[0582] Next, 4.2 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and simultaneously, the supply of 4-tert-butyl benzoic acid vinyl ester was started. A total of 110 g of 4-tert-butyl benzoic acid vinyl ester was added at 2.0 ml / min.

[0583] After the supply of 4-tert-butylbenzoic acid vinyl ester was stopped, the temperature and pressure in the tank were returned to normal to terminate the polymerization, thereby obtaining an acetone solution of 4-tert-butylbenzoic acid vinyl ester / hexafluoropropylene copolymer (solid content concentration: 21% by mass).

[0584] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0585] According to NMR analysis, the obtained fluorine-containing polymer has a composition of 40 mol% of hexafluoropropylene and 60 mol% of 4-tert-butyl benzoic acid vinyl ester. According to molecular weight analysis, the number average molecular weight (Mn) is 9000. The glass transition temperature (Tg) is 110° C. According to the results of elemental analysis, the fluorine content is 25.2% by mass.

[0586] The vinyl ester unit equivalent calculated from the composition was 305 g / eq.

[0587] Synthesis Example 11

[0588] A 3 L stainless steel autoclave was charged with 800 g of acetone as a solvent, 16.5 g of 4-tert-butyl benzoic acid vinyl ester, and 3.5 g of 4-hydroxybutyl vinyl ether, and the autoclave was purged with nitrogen and the tank temperature was raised to 65° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the tank reached 0.79 MPa.

[0589] Then, 2.1 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and the supply of a mixed solution of 180 g of 4-tert-butyl benzoic acid vinyl ester and 37 g of 4-hydroxybutyl vinyl ether was started at the same time. A total of 160 g of the mixed solution of 4-tert-butyl benzoic acid vinyl ester and 37 g of hydroxybutyl vinyl ether was added at 2.0 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction so that the pressure in the tank was 0.775 to 0.7795 MPa.

[0590] After the supply of the mixed solution of 4-tert-butyl benzoic acid vinyl ester and 4-hydroxybutyl vinyl ether was stopped, the supply of tetrafluoroethylene was also stopped, and then the aging reaction was continued at a bath temperature of 70° C. for 0.5 hour.

[0591] Thereafter, the temperature and pressure in the tank were returned to normal to terminate the polymerization, thereby obtaining an acetone solution of 4-tert-butylbenzoic acid vinyl ester / 4-hydroxybutyl vinyl ether / tetrafluoroethylene copolymer (solid content concentration: 14% by mass).

[0592] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0593] According to NMR analysis, the obtained fluorine-containing polymer is composed of 48 mol% of tetrafluoroethylene, 31 mol% of 4-tert-butyl benzoic acid vinyl ester, and 21 mol% of 4-hydroxybutyl vinyl ether. According to molecular weight analysis, the number average molecular weight (Mn) is 10000. The glass transition temperature (Tg) is 40°C. According to the results of elemental analysis, the fluorine content is 26.5% by mass.

[0594] The vinyl ester unit equivalent calculated from the composition was 435 g / eq.

[0595] Synthesis example 12

[0596] A 3 L stainless steel autoclave was charged with 1000 g of acetone and 10 g of vinyl benzoate as solvents, the autoclave was purged with nitrogen, and the tank temperature was raised to 70° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the tank reached 0.79 MPa.

[0597] Next, 4.2 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and simultaneously, a mixed solution of 87 g of vinyl benzoate and 60 g of isobornyl acrylate (IBAC) was started to be supplied. A total of 110 g of the mixed solution of vinyl benzoate and isobornyl acrylate was added at 1.5 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction to keep the pressure in the tank at 0.775 to 0.7795 MPa.

[0598] After the supply of the mixed solution of vinyl benzoate and isobornyl acrylate was stopped, the supply of tetrafluoroethylene was also stopped. The temperature and pressure in the tank were then returned to normal to stop the polymerization, thereby obtaining an acetone solution of a vinyl benzoate / isobornyl acrylate / tetrafluoroethylene copolymer (solid content concentration: 14% by mass).

[0599] After the reaction is completed, the polymer solution is reprecipitated in a large amount of methanol solution, the polymer is purified, and dried to obtain a fluorine-containing polymer.

[0600] According to NMR analysis, the obtained fluorine-containing polymer is composed of 47 mol% of tetrafluoroethylene, 34 mol% of vinyl benzoate, and 19 mol% of isobornyl acrylate. According to molecular weight analysis, the number average molecular weight (Mn) is 8000. The glass transition temperature (Tg) is 60°C. According to the results of elemental analysis, the fluorine content is 26.3% by mass.

[0601] The vinyl ester unit equivalent calculated from the composition was 401 g / eq.

[0602] Synthesis example 13

[0603] 800 g of acetone and 20 g of 4-tert-butyl benzoic acid vinyl ester were placed in a 3 L stainless steel autoclave as a solvent, the autoclave was purged with nitrogen, and the tank temperature was raised to 70° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the tank reached 0.79 MPa.

[0604] Next, 2.1 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and simultaneously the supply of a mixed solution of 100 g of 4-tert-butyl benzoic acid vinyl ester and 54 g of isobornyl acrylate was started. A total of 132 g of the mixed solution of 4-tert-butyl benzoic acid vinyl ester and isobornyl acrylate was added at 1.5 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction to keep the pressure in the tank at 0.775 to 0.7795 MPa.

[0605] After the supply of the mixed solution of 4-tert-butyl benzoic acid vinyl ester and isobornyl acrylate was stopped, the supply of tetrafluoroethylene was also stopped, and then the aging reaction was continued at a tank temperature of 70° C. for 0.5 hour.

[0606] Thereafter, the temperature and pressure in the tank were returned to normal to terminate the polymerization, thereby obtaining an acetone solution of 4-tert-butylbenzoic acid vinyl ester / isobornyl acrylate / tetrafluoroethylene copolymer (solid content concentration: 20% by mass).

[0607] After the reaction is completed, the obtained solution is concentrated and dried to obtain a fluorine-containing polymer.

[0608] According to NMR analysis, the obtained fluorine-containing polymer is composed of 42 mol% of tetrafluoroethylene, 36 mol% of 4-tert-butyl benzoic acid vinyl ester, and 22 mol% of isobornyl acrylate. According to molecular weight analysis, the number average molecular weight (Mn) is 8000. The glass transition temperature (Tg) is 95°C. According to the results of elemental analysis, the fluorine content is 19.8% by mass.

[0609] The vinyl ester unit equivalent calculated from the composition was 450 g / eq.

[0610] Synthesis example 14

[0611] 1400 g of a fluorine-based solvent (Novec 7200 manufactured by 3M) and 20 g of 4-tert-butyl vinyl benzoate were placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the tank temperature was raised to 65° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the tank reached 0.79 MPa.

[0612] Then, 2.1 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and the supply of 4-tert-butyl benzoic acid vinyl ester was started at the same time. A total of 80 g of 4-tert-butyl benzoic acid vinyl ester was added at 2.0 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction to keep the pressure in the tank at 0.775 to 0.7795 MPa.

[0613] After the supply of 4-tert-butylvinyl benzoate was stopped, the supply of tetrafluoroethylene was also stopped.

[0614] Thereafter, the tank was returned to normal temperature and pressure to stop the polymerization, and a solution of 4-tert-butylbenzoic acid vinyl ester / tetrafluoroethylene copolymer in a fluorine-based solvent (solid content concentration 0.4 mass%) was obtained. Since the solid of the fluorinated polymer of 4-tert-butylbenzoic acid vinyl ester / tetrafluoroethylene copolymer was precipitated, 800 g of acetone was further added to the tank, and the mixture was stirred at 60° C. for 0.5 hours to recover the fluorinated polymer. The solid content concentration was 8.3 mass%.

[0615] The obtained acetone solution was concentrated and then reprecipitated in a large amount of methanol solution, and the polymer was purified and dried to obtain a fluorine-containing polymer.

[0616] According to NMR analysis, the obtained fluorine-containing polymer has a composition of 19 mol% of tetrafluoroethylene and 81 mol% of 4-tert-butyl benzoic acid vinyl ester. According to molecular weight analysis, the number average molecular weight (Mn) is 19000. The glass transition temperature (Tg) is 95°C. According to the results of elemental analysis, the fluorine content is 10.4% by mass.

[0617] The vinyl ester unit equivalent calculated from the composition was 236 g / eq.

[0618] Synthesis Example 15

[0619] 1300 g of a fluorine-based solvent (Novec 7200 manufactured by 3M) and 40 g of allyl glycidyl ether were placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the tank temperature was raised to 70° C. Tetrafluoroethylene was added thereto with stirring until the pressure in the tank reached 0.79 MPa.

[0620] Then, 4.2 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and the supply of allyl glycidyl ether was started at the same time. A total of 180 g of allyl glycidyl ether was added at 1.5 ml / min. Tetrafluoroethylene was also continuously supplied during the reaction so that the pressure in the tank was 0.775 to 0.7795 MPa. After the reaction started, 4.2 g of Perbutyl PV was further added after 5 hours, 1 hour, and 1.5 hours.

[0621] After the supply of allyl glycidyl ether was stopped, the supply of tetrafluoroethylene was also stopped.

[0622] Thereafter, the temperature in the tank was further raised to 75° C., and the aging reaction was continued for 3 hours.

[0623] After that, the tank was returned to normal temperature and pressure, the polymerization was stopped, and the contents were discharged, but they were divided into two layers: a solution of a fluorine-based solvent of allyl glycidyl ether / tetrafluoroethylene copolymer (solid content concentration 0.7 mass%) and the main component of allyl glycidyl ether / tetrafluoroethylene copolymer. It is known that allyl glycidyl ether / tetrafluoroethylene copolymer is soluble in acetone, so 800 g of acetone was further added to the tank, stirred at 60°C for 0.5 hours, and the fluorinated polymer was recovered and combined with the previous main component of allyl glycidyl ether / tetrafluoroethylene copolymer. The solid content concentration was 15.2 mass%.

[0624] The obtained acetone solution was concentrated and dried to obtain a fluorine-containing polymer.

[0625] According to NMR analysis, the obtained fluorine-containing polymer (epoxy resin) has a composition of 41 mol% of tetrafluoroethylene and 59 mol% of allyl glycidyl ether. According to molecular weight analysis, the number average molecular weight (Mn) is 1500. The glass transition temperature (Tg) is -35°C. According to the results of elemental analysis, the fluorine content is 28.8% by mass. The property at 25°C is liquid.

[0626] The epoxy unit equivalent calculated from the composition is 184 g / eq.

[0627] Synthesis Example 16

[0628] 800 g of acetone and 20 g of vinyl benzoate as solvents were placed in a 3 L stainless steel autoclave, the autoclave was purged with nitrogen, and the bath temperature was raised to 70° C. 600 g of hexafluoropropylene was placed therein with stirring.

[0629] Next, 4.2 g of Perbutyl PV (product name, manufactured by NOF Corporation) was added as a polymerization initiator, and simultaneously the supply of vinyl benzoate was started. A total of 100 g of vinyl benzoate was added at 1.5 ml / min.

[0630] After the supply of vinyl benzoate was stopped, the temperature and pressure in the tank were returned to normal to terminate the polymerization, thereby obtaining an acetone solution of a vinyl benzoate / hexafluoropropylene copolymer (solid content concentration: 16% by mass).

[0631] After the reaction is completed, the polymer solution is reprecipitated in a large amount of methanol solution, the polymer is purified, and dried to obtain a fluorine-containing polymer.

[0632] According to NMR analysis, the obtained fluorine-containing polymer had a composition of 37 mol% hexafluoropropylene and 63 mol% vinyl benzoate. According to molecular weight analysis, the number average molecular weight (Mn) was 9000. The glass transition temperature (Tg) was 65° C. According to the results of elemental analysis, the fluorine content was 28.1% by mass.

[0633] The vinyl ester unit equivalent calculated from the composition was 235 g / eq.

[0634] [Relative dielectric constant and dielectric loss tangent]

[0635] The films of the fluorinated polymers prepared in Synthesis Examples 1 to 14 and 16 were prepared by vacuum hot pressing. The relative dielectric constant and dielectric loss tangent of the prepared films (sample F) were measured as follows. The results are shown in Table 3.

[0636] The changes in the resonance frequency and Q value of the sample F prepared above were measured using a network analyzer using a cavity resonator, and the dielectric loss tangent (tanδ) at 12 GHz was calculated according to the following formula. The cavity resonator method was performed according to Professor Kobayashi of Saitama University [Non-destructive measurement of the complex dielectric constant of dielectric slab materials based on the cavity resonator method MW87-53].

[0637] tanδ=(1 / Qu)×{1+(W2 / W1)}-(Pc / ωW1)

[0638] [Number 1]

[0639]

[0640] The symbols in the formula are as follows.

[0641] D: Cavity resonator diameter (mm)

[0642] M: Single-side length of cavity resonator (mm)

[0643] L: Sample length (mm)

[0644] c: speed of light (m / s)

[0645] Id: Attenuation (dB)

[0646] F0: Resonance frequency (Hz)

[0647] F1: The high frequency at which the attenuation from the resonance point is 3dB (Hz)

[0648] F2: Low frequency frequency at which the attenuation from the resonance point is 3dB (Hz)

[0649] ε0: Vacuum dielectric constant (H / m)

[0650] εr: relative dielectric constant of the sample

[0651] μ0: vacuum magnetic permeability (H / m)

[0652] Rs: Effective surface resistance taking into account the surface roughness of the conductor cavity (Ω)

[0653] J0: -0.402759

[0654] J1: 3.83171

[0655] -Ratio of CF2H termini

[0656] The results are shown in Table 3.

[0657] -CF2H terminal ratio = (integral value of CF2H from -136 ppm to -142 ppm) / (integral value of CF2 as a whole from -104 ppm to -142 ppm) × 100

[0658] -Ratio of CF2CFHCF3 ends

[0659] The results are shown in Table 3.

[0660] -CF2CFHCF3 terminal ratio = (integral value of CFH from -210ppm to -216ppm) / (integral value of CF from -172ppm to -216ppm) × 100

[0661]

[0662] As can be seen from Table 3, in Synthesis Examples 1 to 7, 9, 10, 12 to 14, and 15 corresponding to the third fluorinated polymer of the present disclosure, the dielectric loss tangent is low.

[0663] Comparison of Synthesis Examples 1 to 3 and comparison of Synthesis Examples 5 and 14 show that the dielectric loss tangent decreases by reducing the ratio of -CF2H terminals.

[0664] Comparison between Synthesis Examples 8 and 16 shows that the dielectric loss tangent decreases by reducing the proportion of -CF2CFHCF3 ends.

[0665] The compatibility evaluation was carried out as follows.

[0666] The fluorinated polymers (ester resins) obtained in Synthesis Examples 1 to 14 and 16 were dissolved in acetone and adjusted to a solid content of 50% by mass. In addition, epoxy resin A: Synthesis Example 15, epoxy resin B: 2,2-bis(4-glycidoxyphenyl)propane (manufactured by Tokyo Chemical Industry Co., Ltd., purity 92.6%, epoxy equivalent 184), and epoxy resin C: ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., epoxy equivalent 130) were also prepared in a solution having a solid content of 50% by mass.

[0667] Next, the two solutions (ester resin solution, epoxy resin solution) were mixed by adjusting the blending amount so that the vinyl ester unit equivalent and the epoxy equivalent were the same. The appearance of the mixed solution was visually observed to evaluate the compatibility. The compatibility evaluation was determined as follows.

[0668] The state of the mixed solution

[0669] Transparent: 0 (good compatibility)

[0670] Opaque: × (poor compatibility)

[0671] When the solid content concentration was 50% by mass and the mixture was not transparent, acetone was added until the mixture became transparent, and the solid content concentration at which the mixture became transparent was used as the compatibility evaluation. The results are shown in Tables 4 to 6. The solid content concentration (% by mass) at which the mixture became transparent is recorded in the column of the compatibility evaluation in the table.

[0672] The reactivity evaluation with the epoxy resin was carried out as follows.

[0673] To the mixed liquid, 0.5% by mass of 4-dimethylaminopyridine (DMAP) was added based on the solid content of the solution, and the mixture was mixed well to prepare a curing composition.

[0674] 10 g of the curable composition was taken and dried in a 50° C. air dryer for 3 hours, and then reacted in a 175° C. air dryer for 12 hours. After the reaction, the cured product was cooled.

[0675] Next, the gel fraction was measured as an index of the reaction degree of the cured product.

[0676] The solidified material was collected and covered with a pre-weighed 400-mesh wire mesh. 25 ml of acetone and the solidified material covered with the wire mesh were added to a 50 ml sample tube, and the solidified material was immersed in acetone for 12 hours. The wire mesh was then removed, dried, and the mass after drying was measured to calculate the mass of the dried solidified material after acetone immersion.

[0677] The gel fraction was calculated as mass of the dried solidified product after immersion in acetone / mass of the solidified product before immersion in acetone×100. The results are shown in Tables 4 to 6.

[0678]

[0679]

[0680]

[0681] As can be seen from Tables 4 to 6, the higher the compatibility (the higher the solid content concentration that reaches transparency), the higher the gel fraction, and the sample using the epoxy resin of Synthesis Example 15 (epoxy resin A) has a high gel fraction.

[0682] As can be seen from Nos. 1 to 3, when vinyl benzoate (VBz) or vinyl acetate is used as the vinyl ester monomer, the reactivity with the epoxy resin is good and the gel fraction is improved.

[0683] From Nos. 5 and 6, it is understood that the use of isobornyl acrylate (IABC) as the third component other than the fluorine-containing vinyl monomer and the vinyl ester monomer improves the reactivity with the epoxy resin and improves the gel fraction.

Claims

1. An epoxy resin comprising a tetrafluoroethylene-based polymerized unit and / or a hexafluoropropylene-based polymerized unit and an allyl glycidyl ether-based polymerized unit, The total content of the tetrafluoroethylene-based polymerized units, the hexafluoropropylene-based polymerized units, and the allyl glycidyl ether-based polymerized units is 98 mol% to 100 mol% based on the total polymerized units, and the allyl glycidyl ether-based polymerized units account for 40 mol% or more of the total polymerized units.

2. The epoxy resin according to claim 1, which is liquid at 25°C.

3. The epoxy resin according to claim 1 or 2, which has a number average molecular weight of 500 to 10,000.

4. The epoxy resin according to claim 1 or 2, characterized in that In the case of containing a polymer unit based on tetrafluoroethylene, the integral value of CF2H at the terminal -CF2H in 19F-NMR is 4% or less relative to the integral value of the entire CF2. When the polymerized unit based on hexafluoropropylene is included, the integrated value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR is 4% or less relative to the integrated value of the entire CF.

5. The epoxy resin according to claim 1 or 2, wherein The polymerized units based on allyl glycidyl ether account for 10 mol% or more of all the polymerized units of the epoxy resin.

6. The epoxy resin according to claim 1 or 2, wherein The total content of the polymerized units derived from tetrafluoroethylene and the polymerized units derived from hexafluoropropylene is 10 mol% or more based on all the polymerized units of the epoxy resin.

7. The epoxy resin according to claim 1 or 2, wherein The epoxy resin comprises tetrafluoroethylene-based polymerized units.

8. The epoxy resin according to claim 1 or 2, wherein The total content of the polymerized units based on tetrafluoroethylene and the polymerized units based on hexafluoropropylene is 40 mol% to 50 mol% based on the total polymerized units of the epoxy resin.

9. A curable composition, characterized in that It comprises the epoxy resin according to any one of claims 1 to 8 and a fluorine-containing polymer, The fluorine-containing polymer comprises polymerization units based on a fluorine-containing vinyl monomer and polymerization units based on a vinyl ester monomer. The total content of the polymerized units based on the fluorine-containing vinyl monomer and the polymerized units based on the vinyl ester monomer is 70 mol% to 100 mol% based on the total polymerized units. The fluorine-containing vinyl monomer comprises at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene and chlorotrifluoroethylene, When the fluorine-containing vinyl monomer includes tetrafluoroethylene, the integral value of CF2H at the terminal of -CF2H in 19F-NMR is 2% or less relative to the integral value of the entire CF2. When the fluorine-containing vinyl monomer includes hexafluoropropylene, the integral value of CFH at the terminal of -CF2CFHCF3 in 19F-NMR is 2% or less relative to the integral value of the entire CF. When the fluorinated vinyl monomer includes chlorotrifluoroethylene, the total integrated value of CF2H at the terminal of -CF2H and the integrated value of CFClH at the terminal of -CFClH in 19F-NMR is 2% or less relative to the total integrated value of the entire CF2 and the entire CFCl. 10 . The curable composition according to claim 9 , further comprising a solvent.

11. The curable composition according to claim 9 or 10, wherein The epoxy resin is contained in an amount of 1 to 1000 parts by mass based on 100 parts by mass of the fluorinated polymer.

12. The curable composition according to claim 9 or 10, further comprising a curing accelerator.

13. A metal-clad laminate comprising a metal foil and a resin layer provided on the metal foil, characterized in that: The resin layer is formed from the curable composition according to any one of claims 9 to 12.

14. The metal-clad laminate according to claim 13, wherein: The metal foil is copper foil.

15. A printed circuit board, characterized in that: The metal foil of the metal-clad laminate according to claim 13 or 14 is etched to form a pattern circuit.

Citation Information

Patent Citations

  • Active ester compound and its use

    JP2006307091A

  • Metal-clad laminate, method of manufacturing the same, and flexible printed circuit board

    JP2012106491A